An independent evaluation of global 1 km soil moisture products using in-situ and airborne observations - Yilin Ma; Liujun Zhu; Shanshui Yuan; Junliang Jin; Zhengyang Tang; Jeffrey P. Walker (Remote Sensing of Environment, 2026)

Influence of diet glyphosate residues on performance and mineral status in group-housed weaning pigs - Martin Tang Sørensen; Uffe Krogh; Ole Højberg; Natalja P. Nørskov; Leslie Foldager (Livestock Science, 2026)

A Bacillus clausii-based biosensor for heavy metal toxicity: Effects of organic substrates on sensitivity and application to electroplating wastewater - Hoang-Duy P. Nguyen; Phuong-Thao T. Le; Duc-Thang Tran; Anh Minh-Nhat Lai; Thanh-Linh H. Duong; Tien-Cuong Hoang; Tang Ba Quang; Nguyen Phuc Thanh Duy; Ta Dang Khoa; Thuy-Phuong T. Pham (International Biodeterioration & Biodegradation, 2026)

Productive, physiological, and biochemical responses of elephant grass ‘BRS Capiaçu’ (Pennisetum purpureum Schumach.) under different water regimes with brackish water in a semi-arid environment - Lara Rosa de Lima-Silva; Lady Daiane Costa de Sousa Martins; Alexandre Maniçoba da Rosa Ferraz Jardim; Wagner Martins dos Santos; Pedro Paulo Santos de Souza; Luciana Sandra Bastos de Souza; Cleber Pereira Alves; Agda Raiany Mota dos Santos; Ênio Farias de França e Silva; Hugo Rafael Bentzen Santos; Wilma Roberta dos Santos; Carlos André Alves de Souza; et al. (Physiology and Molecular Biology of Plants, 2026)
The seasonality of forage production is one of the main challenges in semi-arid regions, where environmental conditions limit agricultural productivity. One promising option is the use of elephant grass ‘BRS Capiaçu’, together with deficit irrigation. This study evaluated the impact of different irrigation depths with brackish water (50%, 75%, 100% and 125% of the reference evapotranspiration – ET 0 ) on the productive, physiological, photochemical and biochemical aspects of ‘BRS Capiaçu’ over two cycles. Irrigation with 50% of the ET 0 resulted in lower rates of net photosynthesis (P n ), with a reduction in photosystem II quantum yield (ΔF/Fm’), qP, NPQ and the electron transport rate (ETR), in addition to greater activity of the antioxidant enzymes superoxide dismutase (SOD), catalase (CAT) and ascorbate peroxidase (APX), indicating oxidative stress. The depths of 50% and 100% of the ET 0 resulted in greater dry matter production, for Cycles 1 and 2, respectively, demonstrating the resilience of the crop to water stress, attributed to such mechanisms of acclimatisation as a reduction in transpiration (T r ) and an increase in water use efficiency. These physiological changes were more obvious during Cycle 2, in which the crop was subjected to lower rainfall (47.8 mm), while salt stress was also more pronounced during this period, in response, the plants showed less water loss through transpiration and larger WUE inst . It was concluded that ‘BRS Capiaçu’ has a high capacity for acclimatisation to semi-arid conditions, and stands out as a viable alternative for mitigating the seasonality of forage production and promoting sustainable livestock farming in the region.

Genomic diversity, inbreeding, and selection signatures in duroc, landrace, and yorkshire pigs from a long-term closed breeding system - Huangyi Tang; Henrique A. Mulim; Shi-Yi Chen; Allan P. Schinckel; Hongfeng-Xue; Dingjie-Qiu; Yizhan-Liu; Hinayah Rojas de Oliveira (Journal of Applied Genetics, 2026)
Duroc (DD), Landrace (LL), and Yorkshire (YY) are among the most widely used commercial pig breeds, having undergone intense long-term selection within closed breeding systems. This study presents a comprehensive genomic analysis of genetic diversity, inbreeding patterns, and selection signatures in DD, LL, and YY populations that have been subject to close breeding for over 15 years. Genomic and pedigree data were available for 1,088 animals (DD = 348, LL = 276, YY = 464), genotyped using the GenoBaits ® Porcine 100 K SNP panel. Principal component analysis and genetic diversity metrics revealed distinct population structures among the three breeds. Pairwise genetic differentiation supported this pattern, with DD showing the greatest divergence from LL (0.34 ± 0.24) and YY (0.33 ± 0.24), while LL and YY were more closely related (FST = 0.22 ± 0.19). Linkage disequilibrium (LD) analysis further confirmed these differences, as DD exhibited the highest average r² (0.34), followed by LL (0.28) and YY (0.25). Within-breed genetic diversity metrics, including observed heterozygosity (HO: 0.37 in DD, 0.39 in LL, 0.38 in YY), expected heterozygosity (HE: 0.36 in DD, 0.37 in LL, 0.38 in YY), and minor allele frequency (MAF: 0.27 in DD, 0.28 in LL, 0.29 in YY), indicated greater genetic variability in LL and YY compared to DD. Runs of homozygosity (ROH) analyses revealed different patterns of autozygosity, with DD exhibiting more long ROH indicative of recent inbreeding, while YY harbored a higher number of short ROH, suggestive of more ancient demographic events. ROH-based inbreeding coefficients (FROH) consistently exceeded pedigree-based estimates (FPED) across all breeds, highlighting the presence of recent or unrecorded inbreeding that pedigree data may not fully capture. According to Generation Proxy Selection Mapping (GPSM), 17, 1, and 12 significant SNPs were detected in DD, LL, and YY, respectively. Functional annotation of ROH islands and GPSM-significant loci revealed both breed-specific and overlapping QTLs related to traits such as growth, reproduction, and carcass. In general, the findings of this study contribute to a deeper understanding of the genomic consequences of long-term closed breeding and provide reference information to support consideration of breeding strategies that balance continued selection for productivity with the maintenance of genetic diversity in modern commercial pig populations.

Determinants of physiological demands, physiological resilience, and muscle fatigability during load carriage in women: an observational trial - Erin E. Robertson; Charlotte V. Coombs; Ella B. Halsall; Christina D. Young; Alice S. Irving; Jonathan C. Y. Tang; Julie P. Greeves; Thomas J. O’Leary (European Journal of Applied Physiology, 2026)

Scanning the horizon for harmful cyanobacterial blooms - Xuexiu Chang; Hugh J. MacIsaac; Ingrid Chorus; George S. Bullerjahn; Rainer Kurmayer; Chi-Yong Ahn; Xiangzhen Kong; Steven W. Wilhelm; Susanna A. Wood; Xiangming Tang; Hans W. Paerl; Sabine Hilt; et al. (Trends in Ecology & Evolution, 2026)

Prenatal and early postnatal lead exposure and later adulthood BMI: The Saint Louis baby tooth – Later life health study - Joyce J.Y. Lin; Ruby Hickman; Michael Leung; Justin Farmer; Ian W. Tang; Kaleigh McAlaine; Tracy Punshon; Brian P. Jackson; Felicitas B. Bidlack; Joseph J. Mangano; Marc G. Weisskopf (Environmental Research, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Persistent disparities in head and neck cancer survival in the United States - Ella P. Jackert; Swar Vimawala; Liyang Tang; Daniel Kwon; Niels Kokot; Tamara Chambers; Uttam Sinha; Yang Chai; Lihua Liu; Albert Y. Han (Cancer Causes & Control, 2026)
Purpose Head and neck cancer (HNC) is a heterogenous disease with substantial mortality. This study assesses the long-term epidemiologic landscape, demographic disparities, and survival outcomes of HNC. Methods Adult patients with primary HNC were identified in the Surveillance, Epidemiology, and End Results (SEER) database by International Classification of Diseases for Oncology (ICD-O) codes. The primary outcomes of this study were overall survival (OS) and cancer-specific survival (CSS). Secondary outcomes included primary tumor site distributions and rates of surgery by race and ethnicity. Multivariable Cox regression modeling was utilized to determine predictors of all-cause and HNC-specific mortality. Results In this cohort of 117,893 head and neck cancer patients, significant racial and ethnic disparities were observed in tumor site, treatment, and outcomes. Black patients were less likely to receive surgery even when accounting for tumor subsite and stage (OR 0.672, 95% CI 0.641–0.705). Five-year overall survival (OS) and cause-specific survival (CSS) were lower in all minority groups ( p < 0.001), with Black patients showing the lowest OS (31.3%) and CSS (58.8%). Multivariable analysis confirmed race/ethnicity, low income (HR 1.043, 95% CI 1.018–1.068), and unmarried status (HR 1.327, 95% CI 1.305–1.350) as independent predictors of increased all-cause and HNC-specific mortality. Conclusion In this most comprehensive and up-to-date analysis of HNC, we demonstrate profound racial and ethnic disparities in tumor sites, treatments, and survival. This study provides critical evidence to guide health policy, resource allocation, and clinical practice aimed at closing longstanding equity gaps in head and neck cancer care.

Diagnosing Linearity Along the Carbon Cascade in Terrestrial Biosphere Models and Observations - Huanyuan Zhang‐Zheng; Vivek K. Arora; Peter Anthoni; Thomas A. M. Pugh; Atul K. Jain; Wenping Yuan; Yadvinder Malhi; Julia Nabel; Daniel S. Goll; Julia Pongratz; Benjamin Poulter; Anthony P. Walker; et al. (Global Change Biology, 2026)
Elevated carbon dioxide (eCO 2 ) acts as a fertiliser for photosynthesis, driving an increase in gross primary production (GPP). However, it is unclear how effectively increased GPP propagates along the ‘carbon (C) cascade’ to increase net primary production (NPP) and vegetation C stocks ( C veg ) in different plant compartments. Vegetation models were criticised for being overly sensitive to photosynthesis (source‐driven), neglecting sink‐driven processes which may attenuate (or amplify) changes in NPP and vegetation C stocks. Here, we introduce an analytical framework to diagnose linearity ( L ) as ratios of relative changes in linked fluxes and pools. We then apply this framework to 16 models of the TRENDY v11 ensemble and to observation‐based estimates of CO 2 sensitivities. We found widely varying global patterns in L across models. Six models showed a majority of grid cells with larger relative changes in NPP than in GPP ( L NPP:GPP > 1 for > 60% of gridcells), indicating increased vegetation carbon use efficiency under eCO 2 . Only three models had L NPP:GPP 60% of gridcells. Four models showed a majority of gridcells with larger relative changes in estimated steady‐state C veg than in NPP, while five models showed the opposite—in both cases with a large spread of L Cveg*:NPP across grid cells within models. Observations‐based analysis reveals median L Cveg*:NPP C veg , ( L Croot:Cveg > 1) while five models showed the opposite. Most field evidence shows L Croot:Cveg > 1. Widely differing distributions of L among models and links in the C cascade reveal a strong influence of nonlinear behaviour in individual models. However, due to the spread in L , across the whole models ensemble, L deviations from 1 were roughly balanced, leading to an overall linear behaviour of terrestrial C cycle representations in the multi‐model‐mean.

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

DeepProfile: An inverse fusion framework for root zone soil moisture profile estimation - Liujun Zhu; Yi Tan; Shanshui Yuan; Junliang Jin; Zhengyang Tang; Jeffrey P. Walker (Remote Sensing of Environment, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Equipping the next generation of plant taxonomists: Insights and recommendations - Ana Rita G. Simões; Frederik Leliaert; Gemma L.C. Bramley; Ruth P. Clark; Rhian J. Smith; Manuel Luján; Ian Ondo; Matilda J.M. Brown; Gabriel K. Ameka; Catherine W. Lukhoba; Renata Borosova; Bente B. Klitgård; et al. (Trends in Plant Science, 2026)

The effects of high-intensity interval training on physical fitness and physiological responses in taekwondo athletes: a systematic review and meta-analysis - Yunzhou Hu; Dinghuang Zhu; Wen Luo; Bingxuan Tang; Yuqing Li; Daniel T. P. Fong; Dan Wang (European Journal of Applied Physiology, 2026)

Identifying ENSO events and their nexus with precipitation and flood dynamics in the Karnali River Basin, Nepal - Tirtha Raj Adhikari; Binod Baniya; Qiuhong Tang; He Li; Suraj Shrestha; Ram Prasad Awasthi; Paul P. J. Gaffney; Yam Prasad Dhital (Natural Hazards, 2026)

Ba isotope unmasks recycling processes of fluid mobile elements in subduction zones - Yang Yu; Xiao-Long Huang; Betchaida D. Payot; Hai-Quan Liu; Ying-De Jiang; Yu Wang; Carla B. Dimalanta; Xin-Feng Ou; Gabriel Theophilus V. Valera; Fan Yang; Graciano P. Yumul; Yi-Gang Xu; et al. (Geochimica et Cosmochimica Acta, 2026)

Soil Fungi Composition and Functional Groups in Phosphate Mine Spontaneous Recovery Areas: A Combined High‐Throughput and Traditional Approaches - Yongsheng Peng; ChengJiao Dao; YuRong Wang; Rong Tang; Neelamanie Yapa; Garumuni Dilrukshi Nadeeshani Menike; Anuruddha Karunarathna; Abdallah M. Elgorban; Alanoud T. Alfagham; Saowaluck Tibpromma; Y. A. P. K. Dayasena; Kai Yan (New Zealand Journal of Botany, 2026)
Our study on the composition and functional groups of soil fungi in phosphate mine spontaneous recovery areas has identified several fungal genera that play a crucial role in soil regeneration. This finding carries significant practical implications for the methodologies employed in mine site reclamation. We used amplicon sequencing‐based high‐throughput sequencing (HTS) and traditional fungal culturing methods in the Kunyang phosphate mining area of Kunming City, Yunnan Province, China, to comprehensively assess fungal community composition and functional diversity during spontaneous regeneration. The fungal communities in the natural recovery area differ significantly from those in the abandoned mining area, exhibiting notably higher fungal diversity indices and a more complex co‐occurrence pattern. Through HTS, 13 fungal phyla and 447 fungal genera were identified. Among them, Ascomycota is the dominant phylum, followed by Basidiomycota , and Mortierella was the primary genus. All cultured fungi belong to Ascomycota , comprising 16 genera, among which Purpureocillium and Penicillium are predominant. The majority of cultured fungi belong to pathogenic and saprophytic groups, while Mortierella is the only potential symbiotic genus. Notably, six fungal genera were identified exclusively through culturable approaches: Aureobasidium , Cladosporium , Cytospora , Discohainesia , Neopyrenochaeta , and Saccharomyces . These genera play a crucial role in soil regeneration, and their identification is a significant step toward understanding their functional characteristics. The results indicate that rhizosphere fungal communities vary significantly under distinct restoration strategies. This underscores the importance of considering regional specificity, such as local climate and soil conditions, when harnessing fungi for vegetation rehabilitation. The synergistic application of high‐throughput sequencing alongside culturable methods is not only beneficial but also crucial for the efficient screening and utilization of functional fungi. This integration reassures professionals in the field about the effectiveness and reliability of their research methods, thereby enhancing their confidence in the outcomes.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Emergent constraints reveal underprediction of future global water availability under anthropogenic forcing - Senlin Tang; Qiang Zhang; Xintong Gong; Chong-Yu Xu; Vijay P. Singh; Fubao Sun; Yao Feng; Ziwei Li; Likun Han (Global and Planetary Change, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Bifidobacterium breve BBr60 Enhances SCFA Levels and Restores NLRP3/NLRP6 Balance in the Gut to Improve Motor Deficits in PD Mice - P. P. An; X. Y. Liang; X. Y. Yao; Z. H. Liao; Y. C. Tang; N. Cao; Z. Wang; W. Wang; H. Y. Niu; C. X. Tang; J. Chen (Probiotics and Antimicrobial Proteins, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

From co-occurrence to co-existence and co-exposure: Associations between per- and polyfluoroalkyl substances and microplastics in the environment - Tianyue Jin; Yaxuan Liu; Jingchun Tang; Hyeong-Moo Shin; Christie M. Sayes; John P. Giesy (Journal of Hazardous Materials, 2025)

AI-Driven scenario discovery: Diffusion models and multi-armed bandits for building control validation - Wei-Ting Tang; Abraham P. Vinod; François Germain; Joel A. Paulson; Christopher R. Laughman; Ankush Chakrabarty (Energy and Buildings, 2025)

Electron diffraction-guided natural product discovery: identification and isolation of new scaffold class from Podospora australis - David A. Delgadillo; Lin Wu; Jessica E. Burch; Lygia Silva de Moraes; Caroline Wang; Benjamin P. Tu; Yi Tang; Hosea M. Nelson (Phytochemistry Letters, 2025)

Efficient removal of ciprofloxacin via photo-Fenton system under circumneutral condition: Performance and mechanism insight - Yongxia Du; Yan Xiao; Yin Xu; Wenzhuo Zhang; Jiahao Feng; Wenwen Zhao; Huiling Tang; Xiaomeng Hai; Jing Xu; Ivan P. Pozdnyakov; Hui Zhang (Journal of Environmental Chemical Engineering, 2025)

Subduction-driven mantle melting controls the magmatic evolution of the early Permian Tianshan orogen - Xiangsong Wang; Shengxuan Tang; Kai Wang; Keda Cai; Min Sun; Guochun Zhao; Ian P. Cawood (Global and Planetary Change, 2025)

Deep learning assisted denoising of fast polychromatic X-ray micro-CT imaging of multiphase flow in porous media - E.S. Mathew; S.J. Jackson; D. Wildenschild; P. Mostaghimi; K. Tang; R.T. Armstrong (Computers & Geosciences, 2025)

The Role of Patient Education in Low Anterior Resection Syndrome: A Systematic Review - P. Tang; R. Tovel; H. Ong; David Proud; Adele Burgess; Eleanor Watson; Wui Yeat Chen; David Lam; Helen Mohan (Journal of Cancer Education, 2025)
Low anterior resection syndrome (LARS) is a significant complication after sphincter-preserving rectal cancer surgery and negatively impacts a patient’s quality of life. Treatment of LARS is multimodal, and many treatments require engagement from the patient. Understanding the complex array of treatment options and the potential additive effects of different therapies can be difficult. This systematic review aims to assess the role of patient education in treatment of LARS in colorectal cancer patients. A systematic literature search was conducted on PubMed, EMBASE and Ovid Medline according to the PRISMA guidelines for articles published from 1946 to October 2023 and registered with PROSPERO: 42,023,434,601. Studies that reported on clinical outcomes of patients with LARS that underwent any educational intervention were included for this review. Results from five publications including 368 patients with LARS were reviewed for analysis. Three interventions were delivered to symptomatic patients postoperatively and two to all patients who underwent low anterior resection preoperatively. Five trial protocols were also included for analysis, including three preoperative and two postoperative interventions Education interventions were often delivered alongside co-interventions such as medications and pelvic floor physiotherapy. Four studies reported improvement of mean LARS scores and quality of life measures related to the education intervention and associated co-interventions. Patient education has a positive impact towards improving functional outcomes in patients with LARS following resection for rectal cancer. In practice, it is often used in conjunction with other interventions. Determining optimal content and delivery methods is a target for future research.

An assessment of maternal concentrations of per- and polyfluoroalkyl substances (PFAS) and trace elements during the second trimester of pregnancy in western Pennsylvania - Natalie F. Price; Alexis Kiyanda; Wan-Yee Tang; Zachary Zimmerman; Janet Catov; Aaron Barchowsky; Aubrey L. Galusha; Kurunthachalam Kannan; Elizabeth J. Mullin; Patrick J. Parsons; Nesta Bortey-Sam; Alison P. Sanders (Environmental Monitoring and Assessment, 2025)

Preoperative Micronutrient Repletion Strategies in Metabolic and Bariatric Surgery: A Systematic Review - Xueying Tang; Dianne P. Reidlinger; Megan Crichton; Lillian Craggs-Dino; Flavia Fayet-Moore; Skye Marshall (Journal of the Academy of Nutrition and Dietetics, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Alpha-cyclodextrin-based polyrotaxane combining phytate lithium salt as a novel bio-based flame-retardant solid polymer electrolyte for all-solid-state lithium metal batteries - Qi Chen; Arnab Ghosh; Wei Tang; Guang-Zhong Yin; Juan P. Fernández-Blázquez; Mingyang Zhang; De-Yi Wang (Chemical Engineering Journal, 2025)

Environmental monitoring for Ascaris egg remediation: a critical review - Nathaniel I. Strong; Jack T. Andraka; Sung-Geun Woo; Sahar H. El Abbadi; Aaron J. Lewis; Sindy K. Y. Tang; Stephen P. Luby; Craig S. Criddle (Environmental Science and Pollution Research, 2025)

Landscapes of gut microbiome and blood metabolomic signatures in relapsing remitting multiple sclerosis - Jinzhou Feng; Shi Tang; Xiaolin Yang; Mengjie Zhang; Zhizhong Li; Shaoru Zhang; Yongliang Han; Yongmei Li; Philippe P. Monnier; Gang Yu; Peng Zheng; Cunjin Zhang; et al. (Science China Life Sciences, 2025)

Can Contaminated Waters from the Fukushima Daiichi NPP Penetrate the East China Sea? - M. V. Budyansky; M. Yu. Uleysky; P. A. Fayman; A. A. Didov; M. A. Lebedeva; A. A. Udalov; T. V. Belonenko; Danling Tang; Xiaobo Yang; Sui Yi (Pure and Applied Geophysics, 2025)

Structure-function effects of different pectin chemistries and its impact on the gastrointestinal immune barrier system - X. Tang; P. de Vos (Critical Reviews in Food Science and Nutrition, 2025)

Development of a bioreactor with an integrated non-dispersive infrared CO2 sensor for rapid and sensitive detection of Cr(VI) toxicity in water - Thanh-Truc H. Phan; Hoang-Duy P. Nguyen; Nguyen-Phuong Nguyen; Hong-Nhung Nguyen; Thanh-Linh H. Duong; Boi-An Tran; Tang Ba Quang; Nguyen Phuc Thanh Duy; Ta Dang Khoa; Thuy-Phuong T. Pham (Journal of Hazardous Materials, 2025)

From soil health to agricultural productivity: The critical role of soil constraint management - Tong Li; Lizhen Cui; Vilim Filipović; Caixian Tang; Yunru Lai; Bernhard Wehr; Xiufang Song; Scott Chapman; Hongdou Liu; Ram C. Dalal; Yash P. Dang (CATENA, 2025)

From Guidelines to Implementation: A Case Study on Applying ICH M10 for Bioanalytical Assay Cross-Validation - Mianzhi Gu; Andrew Gehman; Brady Nifong; Andrew P. Mayer; Vicky Li; Mary Birchler; Kai Wang; Huaping Tang (The AAPS Journal, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Effects of igneous contact metamorphism on the mineral and toxic trace element composition of low-sulfur coal in the Huaibei Coalfield, eastern China - Bingxiang Liu; Xiaopeng Song; Ning Wang; Victor P. Nechaev; Qingli Zhu; Bowen Zhang; Shuhao Tang; Ruoyu Sun (Applied Geochemistry, 2025)

Hydrological responses of three gorges reservoir region (China) to climate and land use and land cover changes - Yixin Sun; Qiang Zhang; Wenlong Song; Senlin Tang; Vijay P. Singh (Natural Hazards, 2025)

Phreatic zone wastewater irrigation: Sensitivity analysis of contaminant fate - Darrell W.S. Tang; Sjoerd E.A.T.M. Van der Zee; Ruud P. Bartholomeus (Journal of Hydrology, 2024)

Training with reduced carbohydrate availability affects markers of bone resorption and formation in male academy soccer players from the English Premier League - Reuben Stables; Liam Anderson; Craig Sale; Marcus P. Hannon; Rachel Dunn; Jonathan C. Y. Tang; William D. Fraser; Nessan B. Costello; Graeme L. Close; James P. Morton (European Journal of Applied Physiology, 2024)
Purpose To test the hypothesis that training with reduced carbohydrate (CHO) availability increases bone resorption in adolescent soccer players. Methods In a randomised crossover design, ten male players (age: 17.4 ± 0.8 years) from an English Premier League academy completed an acute 90-min field-based training session (occurring between 10:30–12:00) in conditions of high (TRAIN HIGH; 1.5 g.kg −1 , 60 g, 1.5 g.kg −1 and 1.5 g.kg −1 consumed at 08:00, during training, 12:30 and 13:30, respectively) or low CHO availability (TRAIN LOW; 0 g.kg −1 ). Participants also completed a non-exercise trial (REST) under identical dietary conditions to TRAIN LOW. Venous blood samples were obtained at 08:30, 10:30, 12:30 and 14:30 for assessment of bone resorption (βCTX), bone formation (PINP) and calcium metabolism (PTH and ACa). Results External training load did not differ (all P > 0.05) between TRAIN HIGH and TRAIN LOW, as evident for total distance (5.6 ± 0.8; 5.5 ± 0.1 km), average speed (81 ± 9; 85 ± 12 m.min −1 ) and high-speed running (350 ± 239; 270 ± 89 m). Area under the curve for both βCTX and PINP was significantly greater ( P < 0.01 and P = 0.03) in TRAIN LOW versus TRAIN HIGH, whilst no differences in PTH or ACa ( P = 0.11 and P = 0.89) were observed between all three trials. Conclusion CHO restriction before, during and after an acute soccer training session increased bone (re)modelling markers in academy players. Despite acute anabolic effects of bone formation, the long-term consequence of bone resorption may impair skeletal development and increase injury risk during growth and maturation.

Improvements and characterization of a microcosmic-based device for sediment erosion - Yuyang Shao; Zhongao Zhang; Yulin Tang; Wei Zhang; Jerome P. -Y. Maa (Frontiers in Marine Science, 2024)
Effective management of sediment transport in water bodies is crucial for maintaining navigational channels and reducing siltation in harbors. This study introduces the first effort in the development of a Field Instrument for Measuring Bed Erosion Response based on microcosmic analysis. The device is designed to automatically measure the sediment bed responses under a series of selected bed shear stresses to determine the critical bed shear stresses for sediment incipient motion and the erosion rates for selected excess bed shear stresses. Numerical simulations were conducted using computational fluid dynamics software (FLUENT) to ensure a reasonable and uniform distribution of the selected bed shear stress across the sediment bed. A lab version of this device was also built and tested using granular sandy sediments and the results were validated against the Shields curve for incipient motion. During this test, however, a problem of sandy bed liquefaction at the bed center was identified because of the pumping out of water at top center. For enhancing the device performances, modifications of the pumping intake were made to eliminate the liquefaction problem. Further a lab test on kaolinite beds with three consolidated durations also demonstrated the capability of this improved device. The study confirms the basic design parameters of the improved device, including the optimal rotating speeds of its pump and disk motors, which are critical for achieving the desired erosion dynamics. These results highlight the potential of the device to significantly improve the precision and efficiency of sediment transport studies in natural aquatic environments.

Displacement prediction of landslides at slope-scale: Review of physics-based and data-driven approaches - Wenping Gong; Shaoyan Zhang; C. Hsein Juang; Huiming Tang; Shiva P. Pudasaini (Earth-Science Reviews, 2024)

Comprehensive ground-motion characterization of the 6 February 2023 $$\:{\varvec{M}}_{\varvec{W}}$$ 7.8 Pazarcık earthquake in Kahramanmaraş, Türkiye: insights into attenuation effects, site responses and source properties - Yuxiang Tang; Karin Şeşetyan; P. Martin Mai (Bulletin of Earthquake Engineering, 2024)

Contamination profile and hazards of neonicotinoid insecticides in honey from apiaries in Beijing, China - Yuan Huang; Benyan Tang; Liming Wu; Chongbo Liang; John P. Giesy; Wanli Li; Yandong Xu; Kai Wang; John R. Purdy; Keith R. Solomon; Suzhen Qi (Environmental Science and Pollution Research, 2024)

Physiologically based pharmacokinetic model to predict drug–drug interactions with the antibody–drug conjugate enfortumab vedotin - Mary P. Choules; Peiying Zuo; Yukio Otsuka; Amit Garg; Mei Tang; Peter Bonate (Journal of Pharmacokinetics and Pharmacodynamics, 2024)
Enfortumab vedotin is an antibody–drug conjugate (ADC) comprised of a Nectin-4–directed antibody and monomethyl auristatin E (MMAE), which is primarily eliminated through P-glycoprotein (P-gp)–mediated excretion and cytochrome P450 3A4 (CYP3A4)–mediated metabolism. A physiologically based pharmacokinetic (PBPK) model was developed to predict effects of combined P-gp with CYP3A4 inhibitor/inducer (ketoconazole/rifampin) on MMAE exposure when coadministered with enfortumab vedotin and study enfortumab vedotin with CYP3A4 (midazolam) and P-gp (digoxin) substrate exposure. A PBPK model was built for enfortumab vedotin and unconjugated MMAE using the PBPK simulator ADC module. A similar model was developed with brentuximab vedotin, an ADC with the same valine-citrulline–MMAE linker as enfortumab vedotin, for MMAE drug–drug interaction (DDI) verification using clinical data. The DDI simulation predicted a less-than-2-fold increase in MMAE exposure with enfortumab vedotin plus ketoconazole (MMAE geometric mean ratio [GMR] for maximum concentration [C max ], 1.15; GMR for area under the time-concentration curve from time 0 to last quantifiable concentration [AUC last ], 1.38). Decreased MMAE exposure above 50% but below 80% was observed with enfortumab vedotin plus rifampin (MMAE GMR C max , 0.72; GMR AUC last , 0.47). No effect of enfortumab vedotin on midazolam or digoxin systemic exposure was predicted. Results suggest that combination enfortumab vedotin, P-gp, and a CYP3A4 inhibitor may result in increased MMAE exposure and patients should be monitored for potential adverse effects. Combination P-gp and a CYP3A4 inducer may result in decreased MMAE exposure. No exposure change is expected for CYP3A4 or P-gp substrates when combined with enfortumab vedotin. ClinicalTrials.gov identifier Not applicable.

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Palygorskite supported nanometer spherical Fe2O3 composite as an effective photocatalyst for peroxymonosulfate activation: Promotion of the Fe(III)/Fe(II) cycle by photogenerated electrons under visible light - Huiling Tang; Yin Xu; Weiping Tang; Yan Xiao; Chi Zhang; Jing Xu; Ivan P. Pozdnyakov; Hui Zhang (Chemical Engineering Journal, 2024)

Ontogenetic variation in isotopic niche positions of aquatic consumers in boreal lakes - T. A. Johnston; P. A. Cott; H. K. Swanson; A. D. Ehrman; G. L. Lescord; A. W. Sumner; P.-L. Savage; K. A. Patterson; R. W.-K. Tang; M. J. Heerschap; J. J. Montgomery; J. M. Gunn (Aquatic Sciences, 2024)

Stratigraphic evidence for a major unconformity within the Ediacaran System - Run Li; Xiqiang Zhou; Michael P. Eddy; Ryan B. Ickert; Zhenfei Wang; Dongjie Tang; Kang-Jun Huang; Peng Peng (Earth and Planetary Science Letters, 2024)

Wildfire smoke impacts lake ecosystems - Mary Jade Farruggia; Janice Brahney; Andrew J. Tanentzap; Jennifer A. Brentrup; Ludmila S. Brighenti; Sudeep Chandra; Alicia Cortés; Rocio L. Fernandez; Janet M. Fischer; Alexander L. Forrest; Yufang Jin; Kenneth Larrieu; et al. (Global Change Biology, 2024)
Wildfire activity is increasing globally. The resulting smoke plumes can travel hundreds to thousands of kilometers, reflecting or scattering sunlight and depositing particles within ecosystems. Several key physical, chemical, and biological processes in lakes are controlled by factors affected by smoke. The spatial and temporal scales of lake exposure to smoke are extensive and under‐recognized. We introduce the concept of the lake smoke‐day, or the number of days any given lake is exposed to smoke in any given fire season, and quantify the total lake smoke‐day exposure in North America from 2019 to 2021. Because smoke can be transported at continental to intercontinental scales, even regions that may not typically experience direct burning of landscapes by wildfire are at risk of smoke exposure. We found that 99.3% of North America was covered by smoke, affecting a total of 1,333,687 lakes ≥10 ha. An incredible 98.9% of lakes experienced at least 10 smoke‐days a year, with 89.6% of lakes receiving over 30 lake smoke‐days, and lakes in some regions experiencing up to 4 months of cumulative smoke‐days. Herein we review the mechanisms through which smoke and ash can affect lakes by altering the amount and spectral composition of incoming solar radiation and depositing carbon, nutrients, or toxic compounds that could alter chemical conditions and impact biota. We develop a conceptual framework that synthesizes known and theoretical impacts of smoke on lakes to guide future research. Finally, we identify emerging research priorities that can help us better understand how lakes will be affected by smoke as wildfire activity increases due to climate change and other anthropogenic activities.

Reactive contaminant infiltration under dynamic preferential flow - Darrell W.S. Tang; Helen K. French; Anton Leijnse; Ruud P. Bartholomeus; Sjoerd E.A.T.M. van der Zee (Journal of Hydrology, 2024)

The natural history and genotype–phenotype correlations of TMPRSS3 hearing loss: an international, multi-center, cohort analysis - Brett M. Colbert; Cris Lanting; Molly Smeal; Susan Blanton; Derek M. Dykxhoorn; Pei-Ciao Tang; Richard L. Getchell; Hedwig Velde; Mirthe Fehrmann; Ryan Thorpe; Prem Chapagain; Heidy Elkhaligy; et al. (Human Genetics, 2024)
TMPRSS3 -related hearing loss presents challenges in correlating genotypic variants with clinical phenotypes due to the small sample sizes of previous studies. We conducted a cross-sectional genomics study coupled with retrospective clinical phenotype analysis on 127 individuals. These individuals were from 16 academic medical centers across 6 countries. Key findings revealed 47 unique TMPRSS3 variants with significant differences in hearing thresholds between those with missense variants versus those with loss-of-function genotypes. The hearing loss progression rate for the DFNB8 subtype was 0.3 dB/year. Post-cochlear implantation, an average word recognition score of 76% was observed. Of the 51 individuals with two missense variants, 10 had DFNB10 with profound hearing loss. These 10 all had at least one of 4 TMPRSS3 variants predicted by computational modeling to be damaging to TMPRSS3 structure and function. To our knowledge, this is the largest study of TMPRSS3 genotype–phenotype correlations. We find significant differences in hearing thresholds, hearing loss progression, and age of presentation, by TMPRSS3 genotype and protein domain affected. Most individuals with TMPRSS3 variants perform well on speech recognition tests after cochlear implant, however increased age at implant is associated with worse outcomes. These findings provide insight for genetic counseling and the on-going design of novel therapeutic approaches.

Effects of Bulleyaconitine A on Extracellular Matrix Secretion and Expression of Related Proteins in Acetaldehyde-Activated Hepatic Stellate Cells - Q. W. Song; Y. P. Yuan; Q. S. Sun; X. D. Zhan; Y. X. Jiang; X. N. Tang (Bulletin of Experimental Biology and Medicine, 2024)

Automated detection of nine infantile fundus diseases and conditions in retinal images using a deep learning system - Yaling Liu; Hai Xie; Xinyu Zhao; Jiannan Tang; Zhen Yu; Zhenquan Wu; Ruyin Tian; Yi Chen; Miaohong Chen; Dimitrios P. Ntentakis; Yueshanyi Du; Tingyi Chen; et al. (EPMA Journal, 2024)

Multi-fidelity Fourier neural operator for fast modeling of large-scale geological carbon storage - Hewei Tang; Qingkai Kong; Joseph P. Morris (Journal of Hydrology, 2024)

The effect of photolysis of sodium citrate treated with gold chloride using coloured light on the generation of gold nanoparticles and the repression of WiDr colon cancer cells - Chien-Wei Cheng; Shwu-Yuan Lee; Shao-Qi Zhan; Cheng-Liang Huang; Tang-Yu Chen; Jeu-Ming P. Yuann; Shiuh-Tsuen Huang; Chi-Ming Chiu; Ji-Yuan Liang (Journal of Photochemistry and Photobiology B: Biology, 2024)

Vegetation−fire feedbacks increase subtropical wildfire risk in scrubland and reduce it in forests - P. Wei; B. Lamont; T. He; W. Xue; P.C. Wang; W. Song; R. Zhang; A.B. Keyhani; S. Zhao; W. Lu; F. Dong; R. Gao; et al. (Journal of Environmental Management, 2024)

Screening Non-neutralizing Anti-idiotype Antibodies Against a Drug Candidate for Total Pharmacokinetic and Target Engagement Assay - Veronica Liu; Kelly McGrath; Josh Albert; Andrew P. Mayer; Maria Busz; Mary Birchler; Huaping Tang; Yong Jiang (The AAPS Journal, 2024)

Occurrence and potential harms of organochlorine pesticides (OCPs) in environment and their removal by periphyton - Cilai Tang; Zhihao Chen; Yingping Huang; Inna P. Solyanikova; S. Venkata Mohan; Hongfeng Chen; Yonghong Wu (Critical Reviews in Environmental Science and Technology, 2023)

Managed phreatic zone recharge for irrigation and wastewater treatment - Darrell W.S. Tang; Sjoerd E.A.T.M. Van der Zee; Dominique M. Narain-Ford; Gé A.P.H. van den Eertwegh; Ruud P. Bartholomeus (Journal of Hydrology, 2023)

Flavor mystery of spicy hot pot base: Chemical understanding of pungent, numbing, umami and fragrant characteristics - Bei Wang; Wei Wu; Jing Liu; Olugbenga P. Soladoye; Chi-Tang Ho; Yuhao Zhang; Yu Fu (Trends in Food Science & Technology, 2023)

S17-02: The Long-term Impact of Perinatal Exposures on Susceptibility to Immune-mediated Diseases - K.A. Rychlik; E.J. Illingworth; S.E. Attreed; S.S. Sanchez; A. Grant-Alfieri; M.C. Rodriguez Steube; A. Mathur; I.F. Sanchez; C. Tang; M. Suresh; G. Lopez-Cecetaite; P. Sadhukhan; et al. (Toxicology Letters, 2023)

Novel ternary Cu0-coupled core-shell Fe0/C nanoparticles micro-electrolysis system toward degradation of organic pollutants: Synergistic effects and removal mechanism - Lin Niu; Xiaoli Zhao; Zhi Tang; Yaqi Cai; Qitao Lei; Deyi Hou; Hongyun Niu; Liangjie Wang; John P. Giesy; Fengchang Wu (Science of The Total Environment, 2023)

Anoxygenic phototrophic arsenite oxidation by a Rhodobacter strain - Yi‐Fei Wu; Jian Chen; Wan‐Ying Xie; Chao Peng; Shi‐Tong Tang; Barry P. Rosen; Andreas Kappler; Jun Zhang; Fang‐Jie Zhao (Environmental Microbiology, 2023)
Microbially mediated arsenic redox transformations are key for arsenic speciation and mobility in rice paddies. Whereas anaerobic anoxygenic photosynthesis coupled to arsenite (As(III)) oxidation has been widely examined in arsenic‐replete ecosystems, it remains unknown whether this light‐dependent process exists in paddy soils. Here, we isolated a phototrophic purple bacteria, Rhodobacter strain CZR27, from an arsenic‐contaminated paddy soil and demonstrated its capacity to oxidize As(III) to arsenate (As(V)) using malate as a carbon source photosynthetically. Genome sequencing revealed an As(III)‐oxidizing gene cluster ( aioXSRBA ) encoding an As(III) oxidase. Functional analyses showed that As(III) oxidation under anoxic phototrophic conditions correlated with transcription of the large subunit of the As(III) oxidase aioA gene. Furthermore, the non‐As(III) oxidizer Rhodobacter capsulatus SB1003 heterologously expressing aioBA from strain CZR27 was able to oxidize As(III), indicating that aioBA was responsible for the observed As(III) oxidation in strain CZR27. Our study provides evidence for the presence of anaerobic photosynthesis‐coupled As(III) oxidation in paddy soils, highlighting the importance of light‐dependent, microbe‐mediated arsenic redox changes in paddy arsenic biogeochemistry.

Revealing the dynamic temperature of the cathode catalyst layer inside proton exchange membrane fuel cell by experimental measurements and numerical analysis - Qianqian Wang; Fumin Tang; Xiang Li; Jim P. Zheng; Liang Hao; Guomin Cui; Pingwen Ming (Chemical Engineering Journal, 2023)

Design of a Patient-Specific Respiratory-Motion-Simulating Platform for In Vitro 4D Flow MRI - Ning Li; Cyril Tous; Ivan P. Dimov; Phillip Fei; Quan Zhang; Simon Lessard; Gerald Moran; Ning Jin; Samuel Kadoury; An Tang; Sylvain Martel; Gilles Soulez (Annals of Biomedical Engineering, 2023)

Review on distribution, fate, and management of potentially toxic elements in incinerated medical wastes - Shiv Bolan; Lokesh P. Padhye; Manish Kumar; Vasileios Antoniadis; Srinidhi Sridharan; Yuanyuan Tang; Narendra Singh; Choolaka Hewawasam; Meththika Vithanage; Lal Singh; Jörg Rinklebe; Hocheol Song; et al. (Environmental Pollution, 2023)

An integrated approach for risk assessment of land subsidence in Xi'an, China using optical and radar satellite images - Fumeng Zhao; Wenping Gong; Huiming Tang; Shiva P. Pudasaini; Tianhe Ren; Zhan Cheng (Engineering Geology, 2023)

Kinetics of support-free interfacial polymerization polyamide films by in-situ absorbance spectroscopy - Jaleh Mansouri; Shiyang Huang; Anthony Agostino; Rhiannon P. Kuchel; Greg Leslie; Chuyang Y. Tang; Anthony G. Fane (Desalination, 2023)

Evolution of diagenetic fluids in the deeply buried, upper Ediacaran Dengying Formation, Central Sichuan Basin, China - Y. J. Hu; C. F. Cai; Y. Li; R. Zhou; Y. J. Tang; J. F. Hu; F. C. Lu; P. Sun (Australian Journal of Earth Sciences, 2023)

Ecological impacts of N-deposition in a remote, high-elevation lake in the Three River Headwaters Region, Qinghai-Tibetan Plateau - Yuxin Luo; Karen J. Taylor; Aaron P. Potito; Karen Molloy; David W. Beilman; Ya Tang (Journal of Paleolimnology, 2023)
This study provides a new record of nitrogen (N) deposition and ecological response at a remote, high-elevation lake within the ecologically fragile Three River Headwaters Region, northwest China, from the early 20 th Century to the past decade. A multi-proxy investigation of a lake sediment core including analyses of chironomids (non-biting midge), lake sediment geochemistry (δ 15 N, δ 13 C, TN, TOC, OC:TN), pollen, non-pollen palynomorphs and 210 Pb-dating. Results were compared with regional pollution forcings, including fertiliser application, atmospheric nitrate and dust deposition, and a localised multiscale air quality modelling system for N-deposition. Our data reflect a mesotrophic lake for the majority of the 20 th Century with minimal anthropogenic impact. A shift in the lake conditions is evident after 1985 with increased nutrient enrichment. Low δ 15 N, OC:TN and increasing TN values, together with an increase in chironomid taxa associated with eutrophic conditions and macrophytes are exhibited in the record, particularly since 2002. These changes are consistent with nutrient loading causing a change in trophic status. Redundancy analysis (RDA) and partial RDAs verified TN as an important driver behind the shift in chironomid community composition in recent decades, explaining 22.2% of the variance on its own and 16.9% with other environmental variables partialled out. While temperature change since 1960 was not a primary control on the chironomid community of Lake Bander, a step-change increase in summer temperatures since the 1990s coincided with the disappearance of cold stenotherms from the record and seems to have exacerbated the shift to more productive conditions. This study highlights the reach of airborne N from modern agricultural and industrial activity to remote locations, and demonstrates the utility of palaeolimnological techniques as part of modern ecosystem assessment for conservation.

Informing the SWAT model with remote sensing detected vegetation phenology for improved modeling of ecohydrological processes - Shouzhi Chen; Yongshuo H. Fu; Zhaofei Wu; Fanghua Hao; Zengchao Hao; Yahui Guo; Xiaojun Geng; Xiaoyan Li; Xuan Zhang; Jing Tang; Vijay P. Singh; Xuesong Zhang (Journal of Hydrology, 2023)

Synergy of surface modified nanoparticles and surfactant in wettability alteration of calcite at high salinity and temperature - Wenyue Tang; Pingkeng Wu; Chang Da; Shehab Alzobaidi; Justin Harris; Brooke Hallaman; Dongdong Hu; Keith P. Johnston (Fuel, 2023)

Gaseous formaldehyde adsorption by eco-friendly, porous bamboo carbon microfibers obtained by steam explosion, carbonization, and plasma activation - Ganmao Su; Jinhui Xiong; Qiushi Li; Siyao Luo; Yupeng Zhang; Tuhua Zhong; David P. Harper; Zhenguan Tang; Linkun Xie; Xijuan Chai; Lianpeng Zhang; Chunhua Wu; et al. (Chemical Engineering Journal, 2023)

Low temperature mechano-catalytic biofuel conversion using liquid metals - Junma Tang; Priyank V. Kumar; Zhenbang Cao; Jialuo Han; Torben Daeneke; Dorna Esrafilzadeh; Anthony P. O'Mullane; Jianbo Tang; Arifur Rahim; Kourosh Kalantar-Zadeh (Chemical Engineering Journal, 2023)

A PadR family transcriptional repressor controls transcription of a trivalent metalloid resistance operon of Azospirillum halopraeferens strain Au 4 - Jun Zhang; Yi‐Fei Wu; Shi‐Tong Tang; Jian Chen; Barry P. Rosen; Fang‐Jie Zhao (Environmental Microbiology, 2022)
Methylarsenite [MAs(III)] is a highly toxic arsenical produced by some microbes as an antibiotic. In this study, we demonstrate that a PadR family transcriptional regulator, PadR ars , from Azospirillum halopraeferens strain Au 4 directly binds to the promoter region of the arsenic resistance ( ars ) operon (consisting of padR ars , arsV , and arsW ) and represses transcription of arsV and arsW genes involved in MAs(III) resistance. Quantitative reverse transcriptase PCR and transcriptional reporter assays showed that transcription of the ars operon is induced strongly by MAs(III) and less strongly by arsenite and antimonite. Electrophoretic mobility shift assays with recombinant PadR ars showed that it represses transcription of the ars operon by binding to two inverted‐repeat sequences within the ars promoter. PadR ars has two conserved cysteine pairs, Cys56/57 and Cys133/134; mutation of the first pair to serine abolished the transcriptional response of the ars operon to trivalent metalloids, suggesting that Cys56/57 form a binding site for trivalent metalloids. Either C133S or C134S derivative responses to MAs(III) but not As(III) or Sb(III), suggesting that it is a third ligand to trivalent metalloids. PadR ars represents a new type of repressor proteins regulating transcription of an ars operon involved in the resistance to trivalent metalloids, especially MAs(III).

Vine water status mapping with multispectral UAV imagery and machine learning - Zhehan Tang; Yufang Jin; Maria Mar Alsina; Andrew J. McElrone; Nicolas Bambach; William P. Kustas (Irrigation Science, 2022)
Optimizing water management has become one of the biggest challenges for grapevine growers in California, especially during drought conditions. Monitoring grapevine water status and stress level across the whole vineyard is an essential step for precision irrigation management of vineyards to conserve water. We developed a unified machine learning model to map leaf water potential ( $${ψ }_{leaf}$$ ψ leaf ), by combining high-resolution multispectral remote sensing imagery and weather data. We conducted six unmanned aerial vehicle (UAV) flights with a five-band multispectral camera from 2018 to 2020 over three commercial vineyards, concurrently with ground measurements of sampled vines. Using vegetation indices from the orthomosaiced UAV imagery and weather data as predictors, the random forest (RF) full model captured 77% of $${ψ }_{leaf}$$ ψ leaf variance, with a root mean square error (RMSE) of 0.123 MPa, and a mean absolute error (MAE) of 0.100 MPa, based on the validation datasets. Air temperature, vapor pressure deficit, and red edge indices such as the normalized difference red edge index (NDRE) were found as the most important variables in estimating $${ψ }_{leaf}$$ ψ leaf across space and time. The reduced RF models excluding weather and red edge indices explained 52–48% of $${ψ }_{leaf}$$ ψ leaf variance, respectively. Maps of the estimated $${ψ }_{leaf}$$ ψ leaf from the RF full model captured well the patterns of both within- and cross-field spatial variability and the temporal change of vine water status, consistent with irrigation management and patterns observed from the ground sampling. Our results demonstrated the utility of UAV-based aerial multispectral imaging for supplementing and scaling up the traditional point-based ground sampling of $${ψ }_{leaf}$$ ψ leaf . The pre-trained machine learning model, driven by UAV imagery and weather data, provides a cost-effective and scalable tool to facilitate data-driven precision irrigation management at individual vine levels in vineyards.

Increased Thermal Challenges Differentially Modulate Neural Plasticity and Stress Responses in Post-Smolt Atlantic Salmon (Salmo salar) - P. A. Tang; N. Gharbi; T. O. Nilsen; M. Gorissen; S. O. Stefansson; L. O. E. Ebbesson (Frontiers in Marine Science, 2022)
The successful transfer of farmed post-smolt Atlantic salmon (Salmo salar) depends on proper stress responses and cognitive functions during the early seawater (SW) phase. However, with increasing summer oceanic temperatures, these processes may become a challenge, implicating allostasis and welfare. Therefore, we examined the effect of post-smolt transfer from 10°C SW to elevated temperatures (13°C, 16°C, and 18°C) on plasma cortisol and telencephalic genes modulating cognition ( neurod, bdnf, pcna , and c-fos ) and stress-axis regulation ( crf, crfbp, mr, gr1, gr2 , and hsd11b2 ). Fish were sampled at i) 1 day following transfer, ii) 45 days of acclimation, and iii) 45 days and 1 h after an acute challenge test (ACT) using confinement stress. Fish transferred to 13°C retained stress responses, elevating levels of cortisol, crf, mr, gr2, c-fos , and bdnf and maintaining levels of neurod and pcna . Contrastingly, although cortisol increased at 16°C, telencephalic genes reverted to an inhibition of stress responses, increasing crfbp and gr1 complemented with dampened bdnf , neurod , and c-fos responses. However, transferring post-smolts to 18°C showed the most adverse effects, having absent stress responses (cortisol and c-fos ), elevated crfbp , and a suppression of hsd11b2 and neurod . The hsd11b2 downregulation implies low cortisol inhibition in line with absent modulations in corticosteroid receptors and stress responses. These results suggest that the transfer to 16°C and 18°C inhibits the normal reactive response of post-smolts. Following acclimation (45 days), cortisol levels were basal for all groups; however, post-smolts at 16°C and 18°C maintained a telencephalic inhibition of key regulatory genes ( crf , mr , gr2 , and hsd11b2 ), alongside a lower mr/gr1 ratio, an indicator of chronic allostatic load. Moreover, neural plasticity ( neurod and pcna ) was suppressed at 16°C and 18°C, suggesting impacts of elevated allostatic loads with potentially inferior cognitive capacities. Despite maintaining similar plasma cortisol responses to ACTs, post-smolts at 16°C and 18°C elevated neural activation ( c-fos ) to stress, implying greater challenges, with the 18°C group also elevating the level of bdnf . In summary, the telencephalon shows that post-smolts transferred to 16°C and 18°C continue to struggle with the thermal allostatic loads even after acclimation, which is not revealed by plasma cortisol levels, grounding the importance of telencephalic measures in identifying environmental thresholds and hidden challenges.

Effects of Wenyang Zhenshuai Granules on the Expression of Key Mitochondrial Autophagy Proteins in the Doxorubicin-Induced Model of H9c2 Cardiomyocyte Injury - L. Q. Peng; X. X. Wu; G. Chen; H. Z. Cai; Y. P. Tang; Q. Y. Chen; X. Y. Chen (Bulletin of Experimental Biology and Medicine, 2022)

Identification of environment types and adaptation zones with self-organizing maps; applications to sunflower multi-environment data in Europe - Daniela Bustos-Korts; Martin P. Boer; Jamie Layton; Anke Gehringer; Tom Tang; Ron Wehrens; Charlie Messina; Abelardo J. de la Vega; Fred A. van Eeuwijk (Theoretical and Applied Genetics, 2022)
Key message We evaluate self-organizing maps (SOM) to identify adaptation zones and visualize multi-environment genotypic responses. We apply SOM to multiple traits and crop growth model output of large-scale European sunflower data. Abstract Genotype-by-environment interactions (G × E) complicate the selection of well-adapted varieties. A possible solution is to group trial locations into adaptation zones with G × E occurring mainly between zones. By selecting for good performance inside those zones, response to selection is increased. In this paper, we present a two-step procedure to identify adaptation zones that starts from a self-organizing map (SOM). In the SOM, trials across locations and years are assigned to groups, called units, that are organized on a two-dimensional grid. Units that are further apart contain more distinct trials. In an iterative process of reweighting trial contributions to units, the grid configuration is learnt simultaneously with the trial assignment to units. An aggregation of the units in the SOM by hierarchical clustering then produces environment types, i.e. trials with similar growing conditions. Adaptation zones can subsequently be identified by grouping trial locations with similar distributions of environment types across years. For the construction of SOMs, multiple data types can be combined. We compared environment types and adaptation zones obtained for European sunflower from quantitative traits like yield, oil content, phenology and disease scores with those obtained from environmental indices calculated with the crop growth model Sunflo. We also show how results are affected by input data organization and user-defined weights for genotypes and traits. Adaptation zones for European sunflower as identified by our SOM-based strategy captured substantial genotype-by-location interaction and pointed to trials in Spain, Turkey and South Bulgaria as inducing different genotypic responses.

Investigating the contribution of white matter hyperintensities and cortical thickness to empathy in neurodegenerative and cerebrovascular diseases - Miracle Ozzoude; Brenda Varriano; Derek Beaton; Joel Ramirez; Melissa F. Holmes; Christopher J. M. Scott; Fuqiang Gao; Kelly M. Sunderland; Paula McLaughlin; Jennifer Rabin; Maged Goubran; Donna Kwan; et al. (GeroScience, 2022)

Secondary metabolites: a boon from plants, the best chemist in nature: preface from the editors - S. Ochatt; A. R. Alan; A. Bhattacharya; C. Hano; K. V. Kiselev; P. L. Marconi; W. C. Otoni; S. Y. Park; K. X. Tang; P. J. Weathers (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Main lymphocyte subpopulations in cerebrospinal fluid and peripheral blood in HIV-1 subtypes C and B - Sergio M. de Almeida; Miriam Perlingeiro Beltrame; Bin Tang; Indianara Rotta; Yara Schluga; Julie Lilian P. Justus; Maria Tadeu da Rocha; Ian Abramson; Florin Vaida; Rachel Schrier; Ronald J. Ellis (Journal of NeuroVirology, 2022)

Navigation of Microrobots by MRI: Impact of Gravitational, Friction and Thrust Forces on Steering Success - Cyril Tous; Ning Li; Ivan P. Dimov; Samuel Kadoury; An Tang; Urs O. Häfeli; Zeynab Nosrati; Katayoun Saatchi; Gerald Moran; Marcus J. Couch; Sylvain Martel; Simon Lessard; et al. (Annals of Biomedical Engineering, 2021)

Freshwater in the Arctic Ocean 2010–2019 - Amy Solomon; Céline Heuzé; Benjamin Rabe; Sheldon Bacon; Laurent Bertino; Patrick Heimbach; Jun Inoue; Doroteaciro Iovino; Ruth Mottram; Xiangdong Zhang; Yevgeny Aksenov; Ronan McAdam; et al. (Ocean Science, 2021)
The Arctic climate system is rapidly transitioning into a new regime with a reduction in the extent of sea ice, enhanced mixing in the ocean and atmosphere, and thus enhanced coupling within the ocean–ice–atmosphere system; these physical changes are leading to ecosystem changes in the Arctic Ocean. In this review paper, we assess one of the critically important aspects of this new regime, the variability of Arctic freshwater, which plays a fundamental role in the Arctic climate system by impacting ocean stratification and sea ice formation or melt. Liquid and solid freshwater exports also affect the global climate system, notably by impacting the global ocean overturning circulation. We assess how freshwater budgets have changed relative to the 2000–2010 period. We include discussions of processes such as poleward atmospheric moisture transport, runoff from the Greenland Ice Sheet and Arctic glaciers, the role of snow on sea ice, and vertical redistribution. Notably, sea ice cover has become more seasonal and more mobile; the mass loss of the Greenland Ice Sheet increased in the 2010s (particularly in the western, northern, and southern regions) and imported warm, salty Atlantic waters have shoaled. During 2000–2010, the Arctic Oscillation and moisture transport into the Arctic are in-phase and have a positive trend. This cyclonic atmospheric circulation pattern forces reduced freshwater content on the Atlantic–Eurasian side of the Arctic Ocean and freshwater gains in the Beaufort Gyre. We show that the trend in Arctic freshwater content in the 2010s has stabilized relative to the 2000s, potentially due to an increased compensation between a freshening of the Beaufort Gyre and a reduction in freshwater in the rest of the Arctic Ocean. However, large inter-model spread across the ocean reanalyses and uncertainty in the observations used in this study prevent a definitive conclusion about the degree of this compensation.

Remodeling of Arctic char ( Salvelinus alpinus ) lipidome under a stimulated scenario of Arctic warming - Chao Wang; Yufeng Gong; Fuchang Deng; Enmin Ding; Jie Tang; Garry Codling; Jonathan K. Challis; Derek Green; Jing Wang; Qiliang Chen; Yuwei Xie; Shu Su; et al. (Global Change Biology, 2021)
Arctic warming associated with global climate change poses a significant threat to populations of wildlife in the Arctic. Since lipids play a vital role in adaptation of organisms to variations in temperature, high‐resolution mass‐spectrometry‐based lipidomics can provide insights into adaptive responses of organisms to a warmer environment in the Arctic and help to illustrate potential novel roles of lipids in the process of thermal adaption. In this study, we studied an ecologically and economically important species—Arctic char ( Salvelinus alpinus )—with a detailed multi‐tissue analysis of the lipidome in response to chronic shifts in temperature using a validated lipidomics workflow. In addition, dynamic alterations in the hepatic lipidome during the time course of shifts in temperature were also characterized. Our results showed that early life stages of Arctic char were more susceptible to variations in temperature. One‐year‐old Arctic char responded to chronic increases in temperature with coordinated regulation of lipids, including headgroup‐specific remodeling of acyl chains in glycerophospholipids (GP) and extensive alterations in composition of lipids in membranes, such as less lyso‐GPs, and more ether‐GPs and sphingomyelin. Glycerolipids (e.g., triacylglycerol, TG) also participated in adaptive responses of the lipidome of Arctic char. Eight‐week‐old Arctic char exhibited rapid adaptive alterations of the hepatic lipidome to stepwise decreases in temperature while showing blunted responses to gradual increases in temperature, implying an inability to adapt rapidly to warmer environments. Three common phosphatidylethanolamines (PEs) (PE 36:6|PE 16:1_20:5, PE 38:7|PE 16:1_22:6, and PE 40:7|PE 18:1_22:6) were finally identified as candidate lipid biomarkers for temperature shifts via machine learning approach. Overall, this work provides additional information to a better understanding of underlying regulatory mechanisms of the lipidome of Arctic organisms in the face of near‐future warming.

Tackling G × E × M interactions to close on-farm yield-gaps: creating novel pathways for crop improvement by predicting contributions of genetics and management to crop productivity - Mark Cooper; Kai P. Voss-Fels; Carlos D. Messina; Tom Tang; Graeme L. Hammer (Theoretical and Applied Genetics, 2021)
Key message Climate change and Genotype-by-Environment-by-Management interactions together challenge our strategies for crop improvement. Research to advance prediction methods for breeding and agronomy is opening new opportunities to tackle these challenges and overcome on-farm crop productivity yield-gaps through design of responsive crop improvement strategies. Abstract Genotype-by-Environment-by-Management (G × E × M) interactions underpin many aspects of crop productivity. An important question for crop improvement is “How can breeders and agronomists effectively explore the diverse opportunities within the high dimensionality of the complex G × E × M factorial to achieve sustainable improvements in crop productivity?” Whenever G × E × M interactions make important contributions to attainment of crop productivity, we should consider how to design crop improvement strategies that can explore the potential space of G × E × M possibilities, reveal the interesting Genotype–Management (G–M) technology opportunities for the Target Population of Environments (TPE), and enable the practical exploitation of the associated improved levels of crop productivity under on-farm conditions. Climate change adds additional layers of complexity and uncertainty to this challenge, by introducing directional changes in the environmental dimension of the G × E × M factorial. These directional changes have the potential to create further conditional changes in the contributions of the genetic and management dimensions to future crop productivity. Therefore, in the presence of G × E × M interactions and climate change, the challenge for both breeders and agronomists is to co-design new G–M technologies for a non-stationary TPE. Understanding these conditional changes in crop productivity through the relevant sciences for each dimension, Genotype, Environment, and Management, creates opportunities to predict novel G–M technology combinations suitable to achieve sustainable crop productivity and global food security targets for the likely climate change scenarios. Here we consider critical foundations required for any prediction framework that aims to move us from the current unprepared state of describing G × E × M outcomes to a future responsive state equipped to predict the crop productivity consequences of G–M technology combinations for the range of environmental conditions expected for a complex, non-stationary TPE under the influences of climate change.

The relationship between niche breadth and range size of beech ( Fagus ) species worldwide - Qiong Cai; Erik Welk; Chengjun Ji; Wenjing Fang; Francesco M. Sabatini; Jianxiao Zhu; Jiangling Zhu; Zhiyao Tang; Fabio Attorre; Juan A. Campos; Andraž Čarni; Milan Chytrý; et al. (Journal of Biogeography, 2021)
Aim This work explores whether the commonly observed positive range size–niche breadth relationship exists for Fagus , one of the most dominant and widespread broad‐leaved deciduous tree genera in temperate forests of the Northern Hemisphere. Additionally, we ask whether the 10 extant Fagus species’ niche breadths and climatic tolerances are under phylogenetic control. Location Northern Hemisphere temperate forests. Taxon Fagus L. Methods Combining the global vegetation database sPlot with Chinese vegetation data, we extracted 107,758 relevés containing Fagus species. We estimated biotic and climatic niche breadths per species using plot‐based co‐occurrence data and a resource‐based approach, respectively. We examined the relationships of these estimates with range size and tested for their phylogenetic signal, prior to which a Random Forest (RF) analysis was applied to test which climatic properties are most conserved across the Fagus species. Results Neither biotic niche breadth nor climatic niche breadth was correlated with range size, and the two niche breadths were incongruent as well. Notably, the widespread North American F. grandifolia had a distinctly smaller biotic niche breadth than the Chinese Fagus species ( F. engleriana , F. hayatae , F. longipetiolata and F. lucida ) with restricted distributions in isolated mountains. The RF analysis revealed that cold tolerance did not differ among the 10 species, and thus may represent an ancestral, fixed trait. In addition, neither biotic nor climatic niche breadths are under phylogenetic control. Main Conclusions We interpret the lack of a general positive range size–niche breadth relationship within the genus Fagus as a result of the widespread distribution, high among‐region variation in available niche space, landscape heterogeneity and Quaternary history. The results hold when estimating niche sizes either by fine‐scale co‐occurrence data or coarse‐scale climate data, suggesting a mechanistic link between factors operating across spatial scales. Besides, there was no evidence for diverging ecological specialization within the genus Fagus .

Assessment of shale gas potential of the lower Permian transitional Shanxi-Taiyuan shales in the southern North China Basin - P. Li; J. C. Zhang; X. Tang; Z. P. Huo; Z. Li; K. Y. Luo; Z. M. Li (Australian Journal of Earth Sciences, 2021)

Projected increase in compound dry and hot events over global land areas - Xinying Wu; Zengchao Hao; Qiuhong Tang; Vijay P. Singh; Xuan Zhang; Fanghua Hao (International Journal of Climatology, 2021)
Under global warming, dry and hot events have been increasing in recent decades and are projected to increase in the future across global land areas. The impacts of compound dry and hot events may lead to increased stress to the natural and human systems than separate dry or hot events. Thus, quantitative assessments of global land areas affected by these compound events are needed to understand their risks. This study focuses on the variation in global land and cropland areas affected by compound dry and hot events for both historical and future periods using observations from Climatic Research Unit (CRU) and simulations from Coupled Model Intercomparison Project Phase 5 (CMIP5) climate models. Based on historical observations and simulations, a substantial increase in the spatial extent of these compound events was detected, especially since the 1980s. Climate model projections under the Representative Concentration Pathway (RCP) 8.5 scenario reveal that both global land and cropland areas affected by compound dry and hot events will increase to approximately 1.7–1.8 times by the end of the 21st century. Based on different thresholds of compound events, the spatial extent of global land areas during the June–July–August (December–January–February) season will increase by 12.38–17.20% (7.83–11.19%) in 2050–2099 relative to that in 1950–1999, and the spatial extent of global cropland areas will increase by 14.69–19.63% (9.60–14.48%). The increase in areas affected by compound dry and hot events may lead to more losses in different sectors in the future and more efforts are needed to cope with their potential impacts.

Application of ornithine-induced regulation in yield formation, grain quality and aroma of fragrant rice - H. W. Luo; P. P. Xing; J. H. Liu; R. F. Lai; L. X. He; T. T. Zhang; X. R. Tang (Cereal Research Communications, 2020)

Evaluating the potential of full‐waveform lidar for mapping pan‐tropical tree species richness - Suzanne M. Marselis; Katharine Abernethy; Alfonso Alonso; John Armston; Timothy R. Baker; Jean‐Francois Bastin; Jan Bogaert; Doreen S. Boyd; Pascal Boeckx; David F. R. P. Burslem; Robin Chazdon; David B. Clark; et al. (Global Ecology and Biogeography, 2020)
Aim Mapping tree species richness across the tropics is of great interest for effective conservation and biodiversity management. In this study, we evaluated the potential of full‐waveform lidar data for mapping tree species richness across the tropics by relating measurements of vertical canopy structure, as a proxy for the occupation of vertical niche space, to tree species richness. Location Tropics. Time period Present. Major taxa studied Trees. Methods First, we evaluated the characteristics of vertical canopy structure across 15 study sites using (simulated) large‐footprint full‐waveform lidar data (22 m diameter) and related these findings to in‐situ tree species information. Then, we developed structure–richness models at the local (within 25–50 ha plots), regional (biogeographical regions) and pan‐tropical scale at three spatial resolutions (1.0, 0.25 and 0.0625 ha) using Poisson regression. Results The results showed a weak structure–richness relationship at the local scale. At the regional scale (within a biogeographical region) a stronger relationship between canopy structure and tree species richness across different tropical forest types was found, for example across Central Africa and in South America [ R 2 ranging from .44–.56, root mean squared difference as a percentage of the mean (RMSD%) ranging between 23–61%]. Modelling the relationship pan‐tropically, across four continents, 39% of the variation in tree species richness could be explained with canopy structure alone ( R 2 = .39 and RMSD% = 43%, 0.25‐ha resolution). Main conclusions Our results may serve as a basis for the future development of a set of structure–richness models to map high resolution tree species richness using vertical canopy structure information from the Global Ecosystem Dynamics Investigation (GEDI). The value of this effort would be enhanced by access to a larger set of field reference data for all tropical regions. Future research could also support the use of GEDI data in frameworks using environmental and spectral information for modelling tree species richness across the tropics.

Transfer of the ph1b gene of ‘Chinese Spring’ into a common wheat cultivar with excellent traits - Y. Li; Q. Li; Y. Li; J. Lan; H. Tang; P. Qi; J. Ma; J. Wang; G. Chen; Z. Pu; W. Li; Z. Li; et al. (Cereal Research Communications, 2020)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

EMS induced SNP changes led to mutation of Wx protein in common wheat - J. Lan; Y. Li; K. Xu; X. Zhang; H. Tang; P. Qi; J. Ma; J. Wang; G. Chen; Z. Pu; W. Li; Z. Li; et al. (Cereal Research Communications, 2020)

Determining Haemodynamic Wall Shear Stress in the Rabbit Aorta In Vivo Using Contrast-Enhanced Ultrasound Image Velocimetry - K. Riemer; E. M. Rowland; C. H. Leow; M. X. Tang; P. D. Weinberg (Annals of Biomedical Engineering, 2020)
Abnormal blood flow and wall shear stress (WSS) can cause and be caused by cardiovascular disease. To date, however, no standard method has been established for mapping WSS in vivo . Here we demonstrate wide-field assessment of WSS in the rabbit abdominal aorta using contrast-enhanced ultrasound image velocimetry (UIV). Flow and WSS measurements were made independent of beam angle, curvature or branching. Measurements were validated in an in silico model of the rabbit thoracic aorta with moving walls and pulsatile flow. Mean errors over a cardiac cycle for velocity and WSS were 0.34 and 1.69%, respectively. In vivo time average WSS in a straight segment of the suprarenal aorta correlated highly with simulations (PC = 0.99) with a mean deviation of 0.29 Pa or 5.16%. To assess fundamental plausibility of the measurement, UIV WSS was compared to an analytic approximation derived from the Poiseuille equation; the discrepancy was 17%. Mapping of WSS was also demonstrated in regions of arterial branching. High time average WSS (TAWSS xz = 3.4 Pa) and oscillatory flow (OSI xz = 0.3) were observed near the origin of conduit arteries. In conclusion, we have demonstrated that contrast-enhanced UIV is capable of measuring spatiotemporal variation in flow velocity, arterial wall location and hence WSS in vivo with high accuracy over a large field of view.

Phylogenetic and population genetic analyses reveal three distinct lineages of the invasive brown root-rot pathogen, Phellinus noxius, and bioclimatic modeling predicts differences in associated climate niches - J. E. Stewart; M.-S. Kim; Y. Ota; N. Sahashi; J. W. Hanna; M. Akiba; J. P. Ata; N. Atibalentja; F. Brooks; C.-L. Chung; E. K. Dann; A. Mohd Farid; et al. (European Journal of Plant Pathology, 2020)

Pyruvate kinase genes in grass carp Ctenopharyngodon idella: molecular characterization, expression patterns, and effects of dietary carbohydrate levels - J. J. Fan; X. H. Tang; J. J. Bai; Dong-Mei Ma; P. Jiang (Fish Physiology and Biochemistry, 2019)

Time and laser ranging: a window of opportunity for geodesy, navigation, and metrology - P. Exertier; A. Belli; E. Samain; W. Meng; H. Zhang; K. Tang; A. Schlicht; U. Schreiber; U. Hugentobler; I. Prochàzka; X. Sun; J. F. McGarry; et al. (Journal of Geodesy, 2019)

Association between occupational exposure to trichloroethylene and serum levels of microRNAs: a cross-sectional molecular epidemiology study in China - Kyoung-Mu Lee; Bryan A. Bassig; Luoping Zhang; Roel C. Vermeulen; Wei Hu; Jason Y. Y. Wong; Chuangyi Qiu; Cuiju Wen; Yongshun Huang; Mark P. Purdue; Bu-Tian Ji; Laiyu Li; et al. (International Archives of Occupational and Environmental Health, 2019)

Effects of fulvic acid on aggregation, sedimentation, and adsorption of Fe3O4 magnetic nanoparticles - Tianhui Zhao; Mengyuan Fang; Zhi Tang; Xiaoli Zhao; Fazhi Xie; Fengchang Wu; John P. Giesy (Environmental Science and Pollution Research, 2019)

Evolving and Sustaining Ocean Best Practices and Standards for the Next Decade - Jay Pearlman; Mark Bushnell; Laurent Coppola; Johannes Karstensen; Pier Luigi Buttigieg; Francoise Pearlman; Pauline Simpson; Michele Barbier; Frank E. Muller-Karger; Cristian Munoz-Mas; Peter Pissierssens; Cyndy Chandler; et al. (Frontiers in Marine Science, 2019)

Immunosignature Analysis of Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) - Oliver P. Günther; Jennifer L. Gardy; Phillip Stafford; Øystein Fluge; Olav Mella; Patrick Tang; Ruth R. Miller; Shoshana M. Parker; Stephen A. Johnston; David M. Patrick (Molecular Neurobiology, 2019)

Parameterization of the modeling variables in velocity analytical solutions of open-channel flows with double-layered vegetation - P. Singh; H. R. Rahimi; X. Tang (Environmental Fluid Mechanics, 2019)

Geochronology, geochemistry and Sr-Nd-Pb-Hf isotopes of the Early Paleogene gabbro and granite from Central Lhasa, southern Tibet: petrogenesis and tectonic implications - Yun-hui Zhang; Hua-wen Cao; Steven P. Hollis; Li Tang; Mo Xu; Jun-sheng Jiang; Shun-bao Gao; Yang-shuang Wang (International Geology Review, 2019)

Indole-3-acetylaspartate and indole-3-acetylglutamate, the IAA-amide conjugates in the diploid strawberry achene, are hydrolyzed in growing seedlings - Qian Tang; Peng Yu; Molly Tillmann; Jerry D. Cohen; Janet P. Slovin (Planta, 2019)

Regulation of glucose metabolism by bioactive phytochemicals for the management of type 2 diabetes mellitus - Chao Zhao; Chengfeng Yang; Sydney Tang Chi Wai; Yanbo Zhang; Maria P. Portillo; Paolo Paoli; Yijing Wu; Wai San Cheang; Bin Liu; Christian Carpéné; Jianbo Xiao; Hui Cao (Critical Reviews in Food Science and Nutrition, 2019)

Geochemistry, zircon U–Pb geochronology and Hf isotopes of Jurassic-Cretaceous granites in the Tengchong terrane, SW China: implications for the Mesozoic tectono-magmatic evolution of the Eastern Tethyan Tectonic Domain - Hua-Wen Cao; Yun-Hui Zhang; Li Tang; Steven P. Hollis; Shou-Ting Zhang; Qiu-Ming Pei; Chang Yang; Xiao-Shuan Zhu (International Geology Review, 2019)

The Be-Well Study: a prospective cohort study of lifestyle and genetic factors to reduce the risk of recurrence and progression of non-muscle-invasive bladder cancer - Marilyn L. Kwan; Lawrence H. Kushi; Kim N. Danforth; Janise M. Roh; Isaac J. Ergas; Valerie S. Lee; Kimberly L. Cannavale; Teresa N. Harrison; Richard Contreras; Ronald K. Loo; David S. Aaronson; Charles P. Quesenberry; et al. (Cancer Causes & Control, 2019)

Using dual isotopes and a Bayesian isotope mixing model to evaluate sources of nitrate of Tai Lake, China - Shasha Liu; Fengchang Wu; Weiying Feng; Wenjing Guo; Fanhao Song; Hao Wang; Ying Wang; Zhongqi He; John P. Giesy; Peng Zhu; Zhi Tang (Environmental Science and Pollution Research, 2018)

Potential impacts of climate change on storage conditions for commercial agriculture: an example for potato production in Michigan - Julie A. Winkler; Logan Soldo; Ying Tang; Todd Forbush; David S. Douches; Chris M. Long; Courtney P. Leisner; C. Robin Buell (Climatic Change, 2018)

The Influence of Water Saturation on the Short- and Long-Term Mechanical Behavior of Red Sandstone - S. B. Tang; C. Y. Yu; M. J. Heap; P. Z. Chen; Y. G. Ren (Rock Mechanics and Rock Engineering, 2018)

Variability in circulating gas emboli after a same scuba diving exposure - V. Papadopoulou; P. Germonpré; D. Cosgrove; R. J. Eckersley; P. A. Dayton; G. Obeid; A. Boutros; M.-X. Tang; S. Theunissen; C. Balestra (European Journal of Applied Physiology, 2018)

Susceptibility profile of echinocandins, azoles and amphotericin B against yeast phase of Talaromyces marneffei isolated from HIV-infected patients in Guangdong, China - H.-L. Lei; L.-H. Li; W.-S. Chen; W.-N. Song; Y. He; F.-Y. Hu; X.-J. Chen; W.-P. Cai; X.-P. Tang (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

The Role of Biomass Composition and Steam Treatment on Durability of Pellets - Yong Tang; Richard P. Chandra; Shahab Sokhansanj; Jack N. Saddler (BioEnergy Research, 2018)

Identifying the germ cells during embryogenesis and gametogenesis by germ‐line gene vasa in an anadromous fish, American shad Alosa sapidissima - X. L. Wu; Z. K. Tang; W. Li; Z. J. Chu; X. Y. Hong; X. P. Zhu; H. Y. Xu (Journal of Fish Biology, 2018)
American shad Alosa sapidissima , an anadromous clupeid, exhibits variation in reproductive strategies, including semelparity and iteroparity. It provides an excellent model for studying the behaviour of germ cells in anadromous fish during their migration from sea to river. The vasa gene was characterized in A. sapidissima as a germ‐cell marker to elaborate the process of germ‐cell development and differentiation in anadromous species. A complementary (c)DNA fragment of 819 bp, partial open reading frame (ORF), was cloned by degenerate PCR and named as ASvas . In adult A. sapidissima , vasa transcript was exclusively detected in gonads by reverse‐transcription (RT)‐PCR. Through chromogenic in situ hybridization, the vasa messenger (m)RNA was specifically detected in primordial germ cells (PGC) in embryos and germ cells at early stages in ovary and testis. Besides, the cellular distribution profile of Vasa protein also proved that vasa gene could be used as a germ‐line marker to trace the PGCs migration during embryogenesis and the germ‐cell differentiation during gametogenesis in A. sapidissima . During embryogenesis, the migrating PGCs were clearly detected at tail‐bud stage and the PGCs reached the genital ridge at the stage of pre‐hatching stage in A. sapidissima embryos. During gametogenesis, the Vasa protein was dynamically expressed in differentiating germ cells at different stages in adult gonads. As far as we know, this is the first report to demonstrate the PGCs migration and germ‐cell differentiation through vasa gene expression in the anadromous species. The findings will pave a way for investigating germ‐cell development and maturation in the A. sapidissima and other anadromous fish.

Impact of choice of future climate change projection on growth chamber experimental outcomes: a preliminary study in potato - Courtney P. Leisner; Joshua C. Wood; Brieanne Vaillancourt; Ying Tang; Dave S. Douches; C. Robin Buell; Julie A. Winkler (International Journal of Biometeorology, 2018)

Amendment of water quality standards in China: viewpoint on strategic considerations - Xiaoli Zhao; Hao Wang; Zhi Tang; Tianhui Zhao; Ning Qin; Huixian Li; Fengchang Wu; John P. Giesy (Environmental Science and Pollution Research, 2018)

Microscopy-based high-throughput assays enable multi-parametric analysis to assess adverse effects of nanomaterials in various cell lines - Iris Hansjosten; Juliane Rapp; Luisa Reiner; Ruben Vatter; Susanne Fritsch-Decker; Ravindra Peravali; Taina Palosaari; Elisabeth Joossens; Kirsten Gerloff; Peter Macko; Maurice Whelan; Douglas Gilliland; et al. (Archives of Toxicology, 2018)

Saurogobio punctatus sp. nov., a new cyprinid gudgeon (Teleostei: Cypriniformes) from the Yangtze River, based on both morphological and molecular data - Q. Y. Tang; X. B. Li; D. Yu; Y. R. Zhu; B. Q. Ding; H. Z. Liu; P. D. Danley (Journal of Fish Biology, 2018)
A new cyprinid gudgeon, Saurogobio punctatus sp. nov., is described based on specimens collected from the Yangtze River, China. The new species can be distinguished from its congeners by differences in both morphology and the cytochrome b ( cytb ) gene sequence. Numerous minute blackish spots are scattered on dorsal and caudal fins in S. punctatus sp. nov. v . absent in the other seven valid Saurogobio species. The new species can be further distinguished from its congeners by the following unique combination of characters: a dorsal fin with eight branched rays; absence of scales in chest area before pectoral origin; upper and lower lips thick, covered with papillae; and a papillose mental pad approximately triangular. Morphologically, the new species most resembles the Chinese lizard gudgeon Saurogobio dabryi , but the new species lays yellowish adhesive eggs v . white pelagic eggs in S. dabryi . A phylogenetic analysis of all Saurogobio species based on cytb gene sequences indicated that S. punctatus sp. nov was distinctly separated from its congeners, with mean sequence divergence ranging from 12·6 to 21·0%. Therefore, molecular data further supported the distinctiveness of the new species.

Low mtDNA variation and shallow population structure of the Chinese pomfret Pampus chinensis along the China coast - P. Sun; B. J. Tang (Journal of Fish Biology, 2018)
In the present study, population genetic structure and genetic diversity of the Chinese pomfret Pampus chinensis , along the China coast were investigated and compared with that from Indonesia using mitochondrial DNA cytochrome b gene sequences. A total of 28 variable sites (including 18 singleton sites and 10 parsimony information sites) were observed and 23 haplotypes were defined in 330 individuals from 11 localities. The haplotype diversity ( H D ) of the populations ranged from 0·540 to 0·828, the nucleotide diversity ( π ) ranged from 0·081 to 0·295%. Pairwise F ST statistics showed that significant genetic divergence occurred among populations from different geographical regions. The high dispersal capabilities, geographic segregation and ocean currents may be responsible for the present population genetic structure in this species. In addition, a population expansion event during the late Pleistocene period was inferred. The time of population expansion was estimated to occur about 117 000–169 000 years ago.

Erratum to: Disruption of mindin exacerbates cardiac hypertrophy and fibrosis - Zhou-Yan Bian; Xiang Wei; Shan Deng; Qi-Zhu Tang; Jinghua Feng; Yan Zhang; Chen Liu; Ding-Sheng Jiang; Ling Yan; Lian-Feng Zhang; Manyin Chen; John Fassett; et al. (Journal of Molecular Medicine, 2017)

The burden and epidemiology of community-acquired central nervous system infections: a multinational study - H. Erdem; A. Inan; E. Guven; S. Hargreaves; L. Larsen; G. Shehata; E. Pernicova; E. Khan; L. Bastakova; S. Namani; A. Harxhi; T. Roganovic; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Top-down cortical interactions in visuospatial attention - Timothy P. Meehan; Steven L. Bressler; Wei Tang; Serguei V. Astafiev; Chad M. Sylvester; Gordon L. Shulman; Maurizio Corbetta (Brain Structure and Function, 2017)

Quality assessment of groundwater from the south-eastern Arabian Peninsula - H. W. Zhang; Y. Q. Sun; Y. Li; X. D. Zhou; X. Z. Tang; P. Yi; A. Murad; S. Hussein; D. Alshamsi; A. Aldahan; Z. B. Yu; X. G. Chen; et al. (Environmental Monitoring and Assessment, 2017)

Examining social and cultural differentiation in early Bronze Age China using stable isotope analysis and mortuary patterning of human remains at Xin’anzhuang, Yinxu - Christina Cheung; Zhichun Jing; Jigen Tang; Zhanwei Yue; Michael P. Richards (Archaeological and Anthropological Sciences, 2017)

Impact of dams on flood occurrence of selected rivers in the United States - Xuefei Mei; P. H. A. J. M. Van Gelder; Zhijun Dai; Zhenghong Tang (Frontiers of Earth Science, 2017)

Aptahistochemistry in diagnostic pathology: technical scrutiny and feasibility - Bakhtiar A. Bukari; Marimuthu Citartan; Ewe Seng Ch’ng; Mawethu P. Bilibana; Timofey Rozhdestvensky; Thean-Hock Tang (Histochemistry and Cell Biology, 2017)

The short-term effects of liming on organic carbon mineralisation in two acidic soils as affected by different rates and application depths of lime - S. P. Grover; C. R. Butterly; X. Wang; C. Tang (Biology and Fertility of Soils, 2017)

Identification of diverse bacterial communities for potential bio-aids capable of troubleshooting for wastewater biological treatment processes - H-W Kuo; C-Y Huang; C-N Chang; P-L Lee; Y-W Chen; C-F Huang; H-H Chang; Y-H Tang; S-Z Zeng; G-Y Li; C-R Lin; L-Z Chen (International Journal of Environmental Science and Technology, 2017)

Cross‐scale intercomparison of climate change impacts simulated by regional and global hydrological models in eleven large river basins - F. F. Hattermann; V. Krysanova; S. N. Gosling; R. Dankers; P. Daggupati; C. Donnelly; M. Flörke; S. Huang; Y. Motovilov; S. Buda; T. Yang; C. Müller; et al. (Climatic Change, 2017)

Pore-scale and continuum simulations of solute transport micromodel benchmark experiments - M. Oostrom; Y. Mehmani; P. Romero-Gomez; Y. Tang; H. Liu; H. Yoon; Q. Kang; V. Joekar-Niasar; M. T. Balhoff; T. Dewers; G. D. Tartakovsky; E. A. Leist; et al. (Computational Geosciences, 2016)

Visual detection technique for efficient screening and isolation of Salmonella based on a novel enrichment assay using chromatography membrane - F. Tang; Y. Xiong; H. Zhang; K. Wu; Y. Xiang; J.-B. Shao; H.-W. Ai; Y.-P. Xiang; X.-L. Zheng; J.-R. Lv; H. Sun; L.-S. Bao; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Functional and genomic insights into the pathogenesis of B urkholderia species to rice - Lynn M. Naughton; Shi‐qi An; Ingyu Hwang; Shan‐Ho Chou; Yong‐Qiang He; Ji‐Liang Tang; Robert P. Ryan; J. Maxwell Dow (Environmental Microbiology, 2016)
Summary A number of species of bacteria from the genus B urkholderia have been shown to be causal agents of diseases of rice. These diseases, caused by B urkholderia glumae , B . gladioli and B . plantarii , are becoming increasingly common across the globe. This is particularly so for B . glumae , whose ability to grow at elevated temperatures suggests that it may become a prevalent problem in an era of global warming. Despite the increasing threat to rice, relatively little is known about the virulence mechanisms employed by these pathogens. Work over the last 5 years has provided an increasing insight into these factors and their control by environmental and other cues. In addition, the determination of a number of genome sequences has allowed bioinformatic predictions of further possible mechanisms, which can now be investigated experimentally. Here, we review recent advances in the understanding of virulence of B urkholderia to rice, to include discussion of the roles of toxins, type II secreted enzymes, type III secreted effectors and motility as well as their regulation by quorum sensing, two‐component systems and cyclic di‐ GMP signalling. Finally, we consider a number of approaches for the control of bacterial virulence through the modulation of quorum sensing and toxin degradation.

Epidemiology and characteristics of the dengue outbreak in Guangdong, Southern China, in 2014 - L. Huang; X. Luo; J. Shao; H. Yan; Y. Qiu; P. Ke; W. Zheng; B. Xu; W. Li; D. Sun; D. Cao; C. Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Analysis of the genome sequence of infectious hematopoietic necrosis virus HLJ-09 in China - C. Wang; L. L. Zhao; Y. J. Li; L. J. Tang; X. Y. Qiao; Y. P. Jiang; M. Liu (Virus Genes, 2016)

A Mesostructure-based Damage Model for Thermal Cracking Analysis and Application in Granite at Elevated Temperatures - Q. L. Yu; P. G. Ranjith; H. Y. Liu; T. H. Yang; S. B. Tang; C. A. Tang; S. Q. Yang (Rock Mechanics and Rock Engineering, 2015)

A review of the plant virus, viroid, liberibacter and phytoplasma records for New Zealand - S. Veerakone; J. Z. Tang; L. I. Ward; L. W. Liefting; Z. Perez-Egusquiza; B. S. M. Lebas; C. Delmiglio; J. D. Fletcher; P. L. Guy (Australasian Plant Pathology, 2015)

Combined blockade of angiotensin II and prorenin receptors ameliorates podocytic apoptosis induced by IgA-activated mesangial cells - Joseph C. K. Leung; Loretta Y. Y. Chan; M. A. Saleem; P. W. Mathieson; Sydney C. W. Tang; Kar Neng Lai (Apoptosis, 2015)

Electrophysiological Differences between the Same Pore Region Mutation in SCN1A and SCN3A - Y.-J. Chen; Y.-W. Shi; H.-Q. Xu; M.-L. Chen; M.-M. Gao; W.-W. Sun; B. Tang; Y. Zeng; W.-P. Liao (Molecular Neurobiology, 2015)

Taxonomy and phylogenetic position of species of Amanita sect. Vaginatae s.l. from tropical Africa - L. P. Tang; Q. Cai; S. S. Lee; B. Buyck; P. Zhang; Zhu L. Yang (Mycological Progress, 2015)

PCDD/Fs in Air and Soil around an E-waste Dismantling Area with Open Burning of Insulated Wires in South China - M. Ren; Y. H. Tang; P. A. Peng; Y. Cai (Bulletin of Environmental Contamination and Toxicology, 2015)

Spatial and temporal distribution and sources of polycyclic aromatic hydrocarbons in sediments of Taihu Lake, eastern China - Zhi Tang; Jianyang Guo; Haiqing Liao; Xiaoli Zhao; Fengchang Wu; Yuanrong Zhu; Liang Zhang; John P. Giesy (Environmental Science and Pollution Research, 2015)

Effect of grazing on the abundance of functional genes associated with N cycling in three types of grassland in Inner Mongolia - K. Ding; L. Zhong; X. P. Xin; Z. H. Xu; X. M. Kang; W. J. Liu; Y. C. Rui; L. L. Jiang; L. Tang; Y. F. Wang (Journal of Soils and Sediments, 2015)

Tsunami Forecast by Joint Inversion of Real-Time Tsunami Waveforms and Seismic or GPS Data: Application to the Tohoku 2011 Tsunami - Yong Wei; Andrew V. Newman; Gavin P. Hayes; Vasily V. Titov; Liujuan Tang (Pure and Applied Geophysics, 2014)

Asymmetric sensitivity of first flowering date to warming and cooling in alpine plants - S. P. Wang; F. D. Meng; J. C. Duan; Y. F. Wang; X. Y. Cui; S. L. Piao; H. S. Niu; G. P. Xu; C. Y. Luo; Z. H. Zhang; X. X. Zhu; M. G. Shen; et al. (Ecology, 2014)
Understanding how flowering phenology responds to warming and cooling (i.e., symmetric or asymmetric response) is needed to predict the response of flowering phenology to future climate change that will happen with the occurrence of warm and cold years superimposed upon a long‐term trend. A three‐year reciprocal translocation experiment was performed along an elevation gradient from 3200 m to 3800 m in the Tibetan Plateau for six alpine plants. Transplanting to lower elevation (warming) advanced the first flowering date (FFD) and transplanting to higher elevation (cooling) had the opposite effect. The FFD of early spring flowering plants (ESF) was four times less sensitive to warming than to cooling (by −2.1 d/°C and 8.4 d/°C, respectively), while midsummer flowering plants (MSF) were about twice as sensitive to warming than to cooling (−8.0 d/°C and 4.9 d/°C, respectively). Compared with pooled warming and cooling data, warming alone significantly underpredicted 3.1 d/°C for ESF and overestimated 1.7 d/°C for MSF. These results suggest that future empirical and experimental studies should consider nonlinear temperature responses that can cause such warming–cooling asymmetries as well as differing life strategies (ESF vs. MSF) among plant species.

Linking continental deep subduction with destruction of a cratonic margin: strongly reworked North China SCLM intruded in the Triassic Sulu UHP belt - J. P. Zheng; H. Y. Tang; Q. Xiong; W. L. Griffin; S. Y. O’Reilly; N. Pearson; J. H. Zhao; Y. B. Wu; J. F. Zhang; Y. S. Liu (Contributions to Mineralogy and Petrology, 2014)

Vitamin D supplementation does not improve human skeletal muscle contractile properties in insufficient young males - Daniel J. Owens; Daniel Webber; Samuel G. Impey; Jonathan Tang; Timothy F. Donovan; William D. Fraser; James P. Morton; Graeme L. Close (European Journal of Applied Physiology, 2014)

Using Bayesian optimization method and FLEXPART tracer model to evaluate CO emission in East China in springtime - X. L. Pan; Y. Kanaya; Z. F. Wang; X. Tang; M. Takigawa; P. Pakpong; F. Taketani; H. Akimoto (Environmental Science and Pollution Research, 2014)

Hydroxymethylation as a Novel Environmental Biosensor - T. Dao; R. Y. S. Cheng; M. P. Revelo; W. Mitzner; W. Y. Tang (Current Environmental Health Reports, 2014)

Erythropoietin Inhibits HIF-1α Expression via Upregulation of PHD-2 Transcription and Translation in an In Vitro Model of Hypoxia–Ischemia - Rhonda Souvenir; Jerry J. Flores; Robert P. Ostrowski; Anatol Manaenko; Kamil Duris; Jiping Tang (Translational Stroke Research, 2014)

Utility of serodiagnostics designed for use in the United States for detection of Lyme borreliosis acquired in Europe and vice versa - Gary P. Wormser; Aimee T. Tang; Natasha R. Schimmoeller; Susan Bittker; Denise Cooper; Paul Visintainer; Maria E. Aguero-Rosenfeld; Katarina Ogrinc; Franc Strle; Gerold Stanek (Medical Microbiology and Immunology, 2014)

Correlations between algae and water quality: factors driving eutrophication in Lake Taihu, China - Y. P. Li; C. Y. Tang; Z. B. Yu; K. Acharya (International Journal of Environmental Science and Technology, 2014)

Receptor Trafficking and the Regulation of Synaptic Plasticity by SUMO - Jia Luo; Emi Ashikaga; Philip P. Rubin; Michaela J. Heimann; Keri L. Hildick; Paul Bishop; Fatima Girach; Fernando Josa-Prado; Leo T. H. Tang; Ruth E. Carmichael; Jeremy M. Henley; Kevin A. Wilkinson (NeuroMolecular Medicine, 2013)

Experimental study on cascading landslide dam failures by upstream flows - Gordon G. D. Zhou; P. Cui; H. Y. Chen; X. H. Zhu; J. B. Tang; Q. C. Sun (Landslides, 2013)

Reliable, verifiable and efficient monitoring of biodiversity via metabarcoding - Yinqiu Ji; Louise Ashton; Scott M. Pedley; David P. Edwards; Yong Tang; Akihiro Nakamura; Roger Kitching; Paul M. Dolman; Paul Woodcock; Felicity A. Edwards; Trond H. Larsen; Wayne W. Hsu; et al. (Ecology Letters, 2013)
To manage and conserve biodiversity, one must know what is being lost, where, and why, as well as which remedies are likely to be most effective. Metabarcoding technology can characterise the species compositions of mass samples of eukaryotes or of environmental DNA . Here, we validate metabarcoding by testing it against three high‐quality standard data sets that were collected in Malaysia (tropical), China (subtropical) and the United Kingdom (temperate) and that comprised 55,813 arthropod and bird specimens identified to species level with the expenditure of 2,505 person‐hours of taxonomic expertise. The metabarcode and standard data sets exhibit statistically correlated alpha‐ and beta‐diversities, and the two data sets produce similar policy conclusions for two conservation applications: restoration ecology and systematic conservation planning. Compared with standard biodiversity data sets, metabarcoded samples are taxonomically more comprehensive, many times quicker to produce, less reliant on taxonomic expertise and auditable by third parties, which is essential for dispute resolution.

Spatial memory and animal movement - William F. Fagan; Mark A. Lewis; Marie Auger‐Méthé; Tal Avgar; Simon Benhamou; Greg Breed; Lara LaDage; Ulrike E. Schlägel; Wen‐wu Tang; Yannis P. Papastamatiou; James Forester; Thomas Mueller (Ecology Letters, 2013)
Memory is critical to understanding animal movement but has proven challenging to study. Advances in animal tracking technology, theoretical movement models and cognitive sciences have facilitated research in each of these fields, but also created a need for synthetic examination of the linkages between memory and animal movement. Here, we draw together research from several disciplines to understand the relationship between animal memory and movement processes. First, we frame the problem in terms of the characteristics, costs and benefits of memory as outlined in psychology and neuroscience. Next, we provide an overview of the theories and conceptual frameworks that have emerged from behavioural ecology and animal cognition. Third, we turn to movement ecology and summarise recent, rapid developments in the types and quantities of available movement data, and in the statistical measures applicable to such data. Fourth, we discuss the advantages and interrelationships of diverse modelling approaches that have been used to explore the memory–movement interface. Finally, we outline key research challenges for the memory and movement communities, focusing on data needs and mathematical and computational challenges. We conclude with a roadmap for future work in this area, outlining axes along which focused research should yield rapid progress.

Pneumonia caused by Aeromonas species in Taiwan, 2004–2011 - C. M. Chao; C. C. Lai; H. Y. Tsai; C. J. Wu; H. J. Tang; W. C. Ko; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Image of a subsurface current core in the southern South China Sea - Q. S. Tang; D. X. Wang; J. B. Li; P. Yan; J. Li (Ocean Science, 2013)
A legacy seismic transect acquired on 30 and 31 May 2009 in the southern South China Sea (SCS) was reprocessed to reveal the thermohaline structure of the water column. In the study region, a mesoscale subsurface lens with extraordinary features was detected at 113.5° E, 11.5° N. It is centred at 450 m depth, occupies both the subsurface and intermediate water from 250 to 600 m, and has an intersection diameter of around 60 km. The simulated results from Hybrid Coordinate Ocean Model reveal an eddy-induced subsurface current running southwestward along the deep basin edge and suggest that the imaged lens is a snapshot of the subsurface current core rather than a subsurface eddy.

QTL analysis of the spring wheat “Chapio” identifies stable stripe rust resistance despite inter-continental genotype × environment interactions - E.-N. Yang; G. M. Rosewarne; S. A. Herrera-Foessel; J. Huerta-Espino; Z.-X. Tang; C.-F. Sun; Z.-L. Ren; R. P. Singh (Theoretical and Applied Genetics, 2013)

3D modeling of stratified and irregularly jointed rock slope and its progressive failure - K. Ma; C. A. Tang; L. C. Li; P. G. Ranjith; M. Cai; N. W. Xu (Arabian Journal of Geosciences, 2013)

Levels, seasonal variations, and health risks assessment of ambient air pollutants in the residential areas - W. C. Zhao; J. P. Cheng; Z. Y. Yu; Q. L. Tang; F. Cheng; Y. W. Yin; W. H. Wang (International Journal of Environmental Science and Technology, 2013)

Splenic Immune Cells in Experimental Neonatal Hypoxia–Ischemia - Nancy Fathali; Robert P. Ostrowski; Yu Hasegawa; Tim Lekic; Jiping Tang; John H. Zhang (Translational Stroke Research, 2013)

Skin and soft-tissue infections caused by Aeromonas species - C. M. Chao; C. C. Lai; H. J. Tang; W. C. Ko; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Polysaccharides of Dendrobium officinale inhibit TNF-α-induced apoptosis in A-253 cell line - L. Xiang; C. W. Stephen Sze; T. B. Ng; Y. Tong; P. C. Shaw; C. W. Sydney Tang; Y. B. Kalin Zhang (Inflammation Research, 2013)

Three-dimensional surface reconstruction of tree canopy from lidar point clouds using a region-based level set method - Shijun Tang; Pinliang Dong; Bill P. Buckles (International Journal of Remote Sensing, 2013)

Biliary tract infections caused by Aeromonas species - C. M. Chao; C. C. Lai; H. J. Tang; W. C. Ko; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Dominantly Inherited Myotonia Congenita Resulting from a Mutation That Increases Open Probability of the Muscle Chloride Channel CLC-1 - David P. Richman; Yawei Yu; Ting-Ting Lee; Pang-Yen Tseng; Wei-Ping Yu; Ricardo A. Maselli; Chih-Yung Tang; Tsung-Yu Chen (NeuroMolecular Medicine, 2012)

Genome-wide association study of glioma and meta-analysis - Preetha Rajaraman; Beatrice S. Melin; Zhaoming Wang; Roberta McKean-Cowdin; Dominique S. Michaud; Sophia S. Wang; Melissa Bondy; Richard Houlston; Robert B. Jenkins; Margaret Wrensch; Meredith Yeager; Anders Ahlbom; et al. (Human Genetics, 2012)

Trogia venenata (Agaricales), a novel poisonous species which has caused hundreds of deaths in southwestern China - Zhu L. Yang; Y. C. Li; L. P. Tang; G. Q. Shi; G. Zeng (Mycological Progress, 2012)

Utility and safety of procalcitonin in an antimicrobial stewardship program (ASP) in patients with malignancies - Y. X. Liew; W. Lee; Y. Y. Cai; J. Teo; S. S.-L. Tang; R. W.-Q. Ong; C. L.-L. Lim; P. B. Lingegowda; A. L.-H. Kwa; M. P. Chlebicki (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Deep placement of organic amendments in dense sodic subsoil increases summer fallow efficiency and the use of deep soil water by crops - J. S. Gill; G. J. Clark; P. W. Sale; R. R. Peries; C. Tang (Plant and Soil, 2012)

Polymorphism of insulin-like growth factor 1 gene and its association with litter size in Small Tail Han sheep - J. N. He; B. Y. Zhang; M. X. Chu; P. Q. Wang; T. Feng; G. L. Cao; R. Di; L. Fang; D. W. Huang; Q. Q. Tang; N. Li (Molecular Biology Reports, 2012)

Disruption of mindin exacerbates cardiac hypertrophy and fibrosis - Zhou-Yan Bian; Xiang Wei; Shan Deng; Qi-Zhu Tang; Jinghua Feng; Yan Zhang; Chen Liu; Ding-Sheng Jiang; Ling Yan; Lian-Feng Zhang; Manyin Chen; John Fassett; et al. (Journal of Molecular Medicine, 2012)

Mycobacterial infections in adult patients with hematological malignancy - C.-Y. Chen; W.-H. Sheng; C.-C. Lai; C.-H. Liao; Y.-T. Huang; W. Tsay; S.-Y. Huang; J.-L. Tang; H.-F. Tien; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Evaluation of the Determine Syphilis TP assay for the detection of antibodies against Treponema pallidum for the serodiagnosis of syphilis - Y.-H. Zhuang; Y. Tian; Y. Chen; J. Tang; J.-Q. Wang; P. Li; Q. Li; Y.-Q. Jiang (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Recent Advances in Biopolymers and Biopolymer-Based Nanocomposites for Food Packaging Materials - X. Z. Tang; P. Kumar; S. Alavi; K. P. Sandeep (Critical Reviews in Food Science and Nutrition, 2012)

Formation and characteristics of post-earthquake debris flow: a case study from Wenjia gully in Mianzhu, Sichuan, SW China - H. Y. Ni; W. M. Zheng; Y. B. Tie; P. C. Su; Y. Q. Tang; R. G. Xu; D. W. Wang; X. Y. Chen (Natural Hazards, 2012)

Diversity of pneumococcal surface protein A (PspA) and relation to sequence typing in Streptococcus pneumoniae causing invasive disease in Chinese children - J. Qian; K. Yao; L. Xue; G. Xie; Y. Zheng; C. Wang; Y. Shang; H. Wang; L. Wan; L. Liu; C. Li; W. Ji; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Clinical and microbiological characteristics of infections caused by various Nocardia species in Taiwan: a multicenter study from 1998 to 2010 - W. L. Liu; C. C. Lai; W. C. Ko; Y. H. Chen; H. J. Tang; Y. L. Huang; Y. T. Huang; P. R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Mechanisms of chloride in cardiomyocyte anoxia-reoxygenation injury: the involvement of oxidative stress and NF-kappaB activation - D. Liu; H. He; G. L. Li; J. Chen; D. Yin; Z. P. Liao; L. Tang; Q. R. Huang; Z. F. Lai; M. He (Molecular and Cellular Biochemistry, 2011)

A novel de novo BRCA1 mutation in a Chinese woman with early onset breast cancer - Ava Kwong; Enders K. O. Ng; Edmund Y. H. Tang; Chris L. P. Wong; Fian B. F. Law; Candy P. H. Leung; Aaron Chan; M. T. Cheung; M. Y. To; Edmond S. K. Ma; Dee W. West; James M. Ford (Familial Cancer, 2011)

Long-term changes in phosphorus fractions in growers’ paddocks in the northern Victorian grain belt - D. T. Vu; R. D. Armstrong; P. J. Newton; C. Tang (Nutrient Cycling in Agroecosystems, 2011)

Genetic association analysis highlights new loci that modulate hematological trait variation in Caucasians and African Americans - Ken Sin Lo; James G. Wilson; Leslie A. Lange; Aaron R. Folsom; Geneviève Galarneau; Santhi K. Ganesh; Struan F. A. Grant; Brendan J. Keating; Steven A. McCarroll; Emile R. Mohler III; Christopher J. O’Donnell; Walter Palmas; et al. (Human Genetics, 2011)

Three-Dimensional Hemodynamics in the Human Pulmonary Arteries Under Resting and Exercise Conditions - Beverly T. Tang; Tim A. Fonte; Frandics P. Chan; Philip S. Tsao; Jeffrey A. Feinstein; Charles A. Taylor (Annals of Biomedical Engineering, 2011)

Formation of melt pocket in mantle peridotite xenolith from western Qinling, Central China: Partial melting and metasomatism - Benxun Su; Hongfu Zhang; Patrick Asamoah Sakyi; Kezhang Qin; Pingping Liu; Jifeng Ying; Yanjie Tang; Sanjeewa P. K. Malaviarachchi; Yan Xiao; Xinmiao Zhao; Qian Mao; Yuguang Ma (Journal of Earth Science, 2010)

Estimating the water budget of major US river basins via remote sensing - Huilin Gao; Qiuhong Tang; Craig R. Ferguson; Eric F. Wood; Dennis P. Lettenmaier (International Journal of Remote Sensing, 2010)

Satellite-based observations of hydrological processes - Qiuhong Tang; Michael Durand; Dennis P. Lettenmaier; Yang Hong (International Journal of Remote Sensing, 2010)

Use of satellite snow-cover data for streamflow prediction in the Feather River Basin, California - Qiuhong Tang; Dennis P. Lettenmaier (International Journal of Remote Sensing, 2010)

Application of nitrogen in NO 3 − form increases rhizosphere alkalisation in the subsurface soil layers in an acid soil - C. Weligama; C. Tang; P. W. G. Sale; M. K. Conyers; D. L. Liu (Plant and Soil, 2010)

Stereological and allometric studies on neurons and axo-dendritic synapses in the superior cervical ganglia of rats, capybaras and horses - Andrzej Loesch; Terry M. Mayhew; Helen Tang; Fernando V. Lobo Ladd; Aliny A. B. Lobo Ladd; Mariana Pereira de Melo; Andrea Almeida P. da Silva; Antonio Augusto Coppi (Cell and Tissue Research, 2010)

Fine mapping of the 9q31 Hirschsprung’s disease locus - C. S. Tang; Y. Sribudiani; X. P. Miao; A. R. de Vries; G. Burzynski; M. T. So; Y. Y. Leon; B. H. Yip; J. Osinga; K. J. W. S. Hui; J. B. G. M. Verheij; S. S. Cherny; et al. (Human Genetics, 2010)

Mutation analysis of the APC gene in Taiwanese FAP families: low incidence of APC germline mutation in a distinct subgroup of FAP families - J. M. Chiang; H. W. Chen; R. P. Tang; J. S. Chen; C. R. Changchien; P. S. Hsieh; J. Y. Wang (Familial Cancer, 2010)

Nitrate leaching stimulates subsurface root growth of wheat and increases rhizosphere alkalisation in a highly acidic soil - C. Weligama; P. W. G. Sale; M. K. Conyers; D. L. Liu; C. Tang (Plant and Soil, 2010)

The role of hydraulic lift and subsoil P placement in P uptake of cotton (Gossypium hirsutum L.) - X. Wang; C. Tang; C. N. Guppy; P. W. G. Sale (Plant and Soil, 2009)

Antimicrobial stewardship program directed at broad-spectrum intravenous antibiotics prescription in a tertiary hospital - V. C. C. Cheng; K. K. W. To; I. W. S. Li; B. S. F. Tang; J. F. W. Chan; S. Kwan; R. Mak; J. Tai; P. Ching; P. L. Ho; W. H. Seto (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

At the Biological Modeling and Simulation Frontier - C. Anthony Hunt; Glen E. P. Ropella; Tai Ning Lam; Jonathan Tang; Sean H. J. Kim; Jesse A. Engelberg; Shahab Sheikh-Bahaei (Pharmaceutical Research, 2009)

Positive Allosteric Interaction of Structurally Diverse T-Type Calcium Channel Antagonists - Victor N. Uebele; Cindy E. Nuss; Steven V. Fox; Susan L. Garson; Razvan Cristescu; Scott M. Doran; Richard L. Kraus; Vincent P. Santarelli; Yuxing Li; James C. Barrow; Zhi-Qiang Yang; Kelly-Ann S. Schlegel; et al. (Cell Biochemistry and Biophysics, 2009)

Variations of chlorophyll- a in the northeastern Indian Ocean after the 2004 South Asian tsunami - Danling Tang; Hui Zhao; B. Satyanarayana; Guangming Zheng; Ramesh P. Singh; Jianhai Lv; Zhongzheng Yan (International Journal of Remote Sensing, 2009)

Comparison of Approaches to Calibrate a Surface Complexation Model for U(VI) Sorption to Weathered Saprolite - F. Zhang; J. C. Parker; S. C. Brooks; Y.-J. Kim; G. Tang; P. M. Jardine; D. B. Watson (Transport in Porous Media, 2009)

Construction, Characterization, and Expressed Sequence Tag (EST) Analysis of Normalized cDNA Library of Thermo-Photoperiod-Sensitive Genic Male Sterile (TPGMS) Wheat from Spike Developmental Stages - D. Yang; Z. H. Tang; L. P. Zhang; C. P. Zhao; Y. L. Zheng (Plant Molecular Biology Reporter, 2009)

Time-Dependent Oxidative Stress Responses of Crucian Carp (Carassius auratus) to Intraperitoneal Injection of Extracted Microcystins - X. Zhang; P. Xie; D. Li; R. Tang; H. Lei; Y. Zhao (Bulletin of Environmental Contamination and Toxicology, 2009)

Modeling the Effects of Heterogeneity and Anisotropy on the Excavation Damaged/Disturbed Zone (EDZ) - S. H. Wang; C. I. Lee; P. G. Ranjith; C. A. Tang (Rock Mechanics and Rock Engineering, 2009)

Aflatoxin–albumin adducts and correlation with decreased serum levels of vitamins A and E in an adult Ghanaian population - L. Tang; L. Xu; E. Afriyie-Gyawu; W. Liu; P. Wang; Y. Tang; Z. Wang; H.J. Huebner; N.-A. Ankrah; D. Ofori-Adjei; J.H. Williams; J.-S. Wang; et al. (Food Additives & Contaminants: Part A, 2009)

Phosphorus acquisition characteristics of cotton (Gossypium hirsutum L.), wheat (Triticum aestivum L.) and white lupin (Lupinus albus L.) under P deficient conditions - X. Wang; C. Tang; C. N. Guppy; P. W. G. Sale (Plant and Soil, 2008)

Localised nitrate and phosphate application enhances root proliferation by wheat and maximises rhizosphere alkalisation in acid subsoil - C. Weligama; C. Tang; P. W. G. Sale; M. K. Conyers; D. L. Liu (Plant and Soil, 2008)

Simulation of direct effects of black carbon aerosol on temperature and hydrological cycle in Asia by a Regional Climate Model - J. Wu; C. Fu; Y. Xu; J. P. Tang; W. Wang; Z. Wang (Meteorology and Atmospheric Physics, 2008)

Validation and comparison of 1 km global land cover products in China - W. Wu; R. Shibasaki; P. Yang; L. Ongaro; Q. Zhou; H. Tang (International Journal of Remote Sensing, 2008)

Inhibition of the development of collagen-induced arthritis in Wistar rats through vagus nerve suspension: a 3-month observation - P. Zhang; D. Han; T. Tang; X. Zhang; K. Dai (Inflammation Research, 2008)

Complete genomic sequence of a Papaya ringspot virus isolate from Hainan Island, China - Y. W. Lu; W. T. Shen; P. Zhou; Q. J. Tang; Y. M. Niu; M. Peng; Z. Xiong (Archives of Virology, 2008)

Variations of ocean colour parameters with nonuniform vertical profiles of chlorophyll concentration - P. Xiu; Y. Liu; J. Tang (International Journal of Remote Sensing, 2008)

CO 2 balance of boreal, temperate, and tropical forests derived from a global database - S. LUYSSAERT; I. INGLIMA; M. JUNG; A. D. RICHARDSON; M. REICHSTEIN; D. PAPALE; S. L. PIAO; E. ‐D. SCHULZE; L. WINGATE; G. MATTEUCCI; L. ARAGAO; M. AUBINET; et al. (Global Change Biology, 2007)
Terrestrial ecosystems sequester 2.1 Pg of atmospheric carbon annually. A large amount of the terrestrial sink is realized by forests. However, considerable uncertainties remain regarding the fate of this carbon over both short and long timescales. Relevant data to address these uncertainties are being collected at many sites around the world, but syntheses of these data are still sparse. To facilitate future synthesis activities, we have assembled a comprehensive global database for forest ecosystems, which includes carbon budget variables (fluxes and stocks), ecosystem traits (e.g. leaf area index, age), as well as ancillary site information such as management regime, climate, and soil characteristics. This publicly available database can be used to quantify global, regional or biome‐specific carbon budgets; to re‐examine established relationships; to test emerging hypotheses about ecosystem functioning [e.g. a constant net ecosystem production (NEP) to gross primary production (GPP) ratio]; and as benchmarks for model evaluations. In this paper, we present the first analysis of this database. We discuss the climatic influences on GPP, net primary production (NPP) and NEP and present the CO 2 balances for boreal, temperate, and tropical forest biomes based on micrometeorological, ecophysiological, and biometric flux and inventory estimates. Globally, GPP of forests benefited from higher temperatures and precipitation whereas NPP saturated above either a threshold of 1500 mm precipitation or a mean annual temperature of 10 °C. The global pattern in NEP was insensitive to climate and is hypothesized to be mainly determined by nonclimatic conditions such as successional stage, management, site history, and site disturbance. In all biomes, closing the CO 2 balance required the introduction of substantial biome‐specific closure terms. Nonclosure was taken as an indication that respiratory processes, advection, and non‐CO 2 carbon fluxes are not presently being adequately accounted for.

Soluble Neuroprotective Antioxidant Uric Acid Analogs Ameliorate Ischemic Brain Injury in Mice - Frank Haberman; Sung-Chun Tang; Thiruma V. Arumugam; Dong-Hoon Hyun; Qian-Sheng Yu; Roy G. Cutler; Zhihong Guo; Harold W. Holloway; Nigel H. Greig; Mark P. Mattson (NeuroMolecular Medicine, 2007)

Comparison of four infectious bursal disease viruses isolated from different bird species - Y. S. Wang; Z. C. Wang; Y. D. Tang; Z. L. Shi; K. W. He; Y. Li; J. B. Hou; H. C. Yao; H. J. Fan; C. P. Lu (Archives of Virology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Multi‐sensor studies of the Sumatra earthquake and tsunami of 26 December 2004 - R. P. Singh; G. Cervone; M. Kafatos; A. K. Prasad; A. K. Sahoo; D. Sun; D. L. Tang; R. Yang (International Journal of Remote Sensing, 2007)

Ganoderma lucidum polysaccharide peptide reduced the production of proinflammatory cytokines in activated rheumatoid synovial fibroblast - Y. W. Ho; J. S. L. Yeung; P. K. Y. Chiu; W. M. Tang; Z. B. Lin; R. Y. K. Man; C. S. Lau (Molecular and Cellular Biochemistry, 2007)

Numerical Modelling of the Heterogeneous Rock Fracture Process Using Various Test Techniques - H. Y. Liu; S. Q. Kou; P.-A. Lindqvist; C. A. Tang (Rock Mechanics and Rock Engineering, 2007)

The LRRK2 Gly2385Arg variant is associated with Parkinson’s disease: genetic and functional evidence - E. K. Tan; Y. Zhao; L. Skipper; M. G. Tan; A. Di Fonzo; L. Sun; S. Fook-Chong; S. Tang; E. Chua; Y. Yuen; L. Tan; R. Pavanni; et al. (Human Genetics, 2007)

Functional analysis of members of the isoflavone and isoflavanone O-methyltransferase enzyme families from the model legume Medicago truncatula - Bettina E. Deavours; Chang-Jun Liu; Marina A. Naoumkina; Yuhong Tang; Mohamed A. Farag; Lloyd W. Sumner; Joseph P. Noel; Richard A. Dixon (Plant Molecular Biology, 2006)

Impact of post-synaptic block of neuromuscular transmission, muscle unloading and mechanical ventilation on skeletal muscle protein and mRNA expression - H. Norman; J. Nordquist; P. Andersson; T. Ansved; X. Tang; B. Dworkin; L. Larsson (Pflügers Archiv - European Journal of Physiology, 2006)

Role of the JAK-STAT pathway in protection of hydrogen peroxide preconditioning against apoptosis induced by oxidative stress in PC12 cells - H. M. Yu; J. L. Zhi; Y. Cui; E. H. Tang; S. N. Sun; J. Q. Feng; P. X. Chen (Apoptosis, 2006)

Curcumin protects PC12 cells against 1-methyl-4-phenylpyridinium ion-induced apoptosis by bcl-2-mitochondria-ROS-iNOS pathway - J. Chen; X. Q. Tang; J. L. Zhi; Y. Cui; H. M. Yu; E. H. Tang; S. N. Sun; J. Q. Feng; P. X. Chen (Apoptosis, 2006)

Industrial wideband noise reduction for hearing aids using a headset with adaptive-feedback active noise cancellation - J. -H. Lin; P. -C. Li; S. -T. Tang; P. -T. Liu; S. -T. Young (Medical & Biological Engineering & Computing, 2005)

On Tension Failure of 2-D Rock Specimens and Associated Acoustic Emission - L. G. Tham; H. Liu; C. A. Tang; P. K. K. Lee; Y. Tsui (Rock Mechanics and Rock Engineering, 2005)

Population Structure of Tropical Abalone (Haliotis asinina) in Coastal Waters of Thailand Determined Using Microsatellite Markers - S. Tang; A. Tassanakajon; S. Klinbunga; P. Jarayabhand; P. Menasveta (Marine Biotechnology, 2004)

Evaluation of the bioremediatory potential of several species of the red alga Porphyra using short-term measurements of nitrogen uptake as a rapid bioassay - George P. Kraemer; Raquel Carmona; Thierry Chopin; Christopher Neefus; Xiaorong Tang; Charles Yarish (Journal of Applied Phycology, 2004)

Biodegradation and detoxification of nicotine in tobacco solid waste by a Pseudomonas sp. - S.N. Wang; P. Xu; H.Z. Tang; J. Meng; X.L. Liu; J. Huang; H. Chen; Y. Du; H.D. Blankespoor (Biotechnology Letters, 2004)

Heart-type fatty acid binding proteins are upregulated during terminal differentiation of mouse cardiomyocytes, as revealed by proteomic analysis - M. K. Tang; P. M. Kindler; D. Q. Cai; P. H. Chow; M. Li; K. K. H. Lee (Cell and Tissue Research, 2004)

One hundred and one new microsatellite loci derived from ESTs (EST-SSRs) in bread wheat - L. F. Gao; R. L. Jing; N. X. Huo; Y. Li; X. P. Li; R. H. Zhou; X. P. Chang; J. F. Tang; Z. Y. Ma; J. Z. Jia (Theoretical and Applied Genetics, 2004)

Proton release of two genotypes of bean (Phaseolus vulgaris L.) as affected by N nutrition and P deficiency - C. Tang; J.J. Drevon; B. Jaillard; G. Souche; P. Hinsinger (Plant and Soil, 2004)

Effect of Stenosis Asymmetry on Blood Flow and Artery Compression: A Three-Dimensional Fluid-Structure Interaction Model - Dalin Tang; Chun Yang; Shunichi Kobayashi; Jie Zheng; Raymond P. Vito (Annals of Biomedical Engineering, 2003)

Seasonal photosynthesis and water relations of juvenile loblolly pine relative to stand density and canopy position - Zhenmin Tang; Jim L. Chambers; Mary A. Sword; James P. Barnett (Trees, 2003)

Modelling the distribution, sustainability and diapause emergence timing of the copepod Calanus finmarchicus in the Labrador Sea - D. P. Tittensor; B. DeYoung; C. L. Tang (Fisheries Oceanography, 2003)
It is now recognized that Calanus finmarchicus , the dominant copepod zooplankter of the North Atlantic, has most of its biomass in the open ocean. While the Labrador Sea does contain a large population of Calanus finmarchicus , the importance of possible connections with the rest of the North Atlantic are not understood. Although there are few wintertime observations, sufficient data exist to model the role of the circulation, temperature and food supply on population dynamics. This study couples a biological model of Calanus finmarchicus with a physical oceanographic model of the Labrador Sea, using chlorophyll data derived from observations by the satellite‐borne SeaWiFS (Sea‐viewing Wide Field‐of‐view Sensor) as a proxy food supply for the numerical copepods. We produce a large‐scale, comprehensive picture of the spatial distribution of Calanus finmarchicus in the Labrador Sea, along with an exploration of the timing of diapause and an examination of population sustainability. We are able to simulate reasonably well the temporal and spatial patterns of Calanus finmarchicus in the Labrador Sea. During a year long model run, the population has a single generation over most of the Labrador Sea, with a final diapausing population about 50% the size of the initial for the parameters used in these simulations. A latitudinally dependent diapause emergence scheme with early emergence to the south of Newfoundland provides the best fit to data. A change of 0.5°C in the temperature field can cause significant changes in the population abundance in a single year, due to changes in Calanus finmarchicus growth rates.

Neuroscience data and tool sharing - Peter Eckersley; Gary F. Egan; Erik De Schutter; Tang Yiyuan; Mirko Novak; Vaclav Sebesta; Line Matthiessen; Irio P. Jaaskelainen; Ulla Ruotsalainen; Andreas V. M. Herz; Klaus-Peter Hoffmann; Raphael Ritz; et al. (Neuroinformatics, 2003)

Himalayan magmatism and porphyry copper-molybdenum mineralization in the Yulong ore belt, East Tibet - X. X. Gu; J. X. Tang; C. S. Wang; J. P. Chen; B. B. He (Mineralogy and Petrology, 2003)

Increasing embryogenesis and doubling efficiency by immediate colchicine treatment of isolated microspores in spring Brassica napus - W.J. Zhou; P. Hagberg; G.X. Tang (Euphytica, 2002)

Genetic diversity of winter wheat in Shaanxi province, China, and other common wheat germplasm pools - Samuel P. Hazen; Lieceng Zhu; Hong-Sik Kim; Guoshiun Tang; Richard W. Ward (Genetic Resources and Crop Evolution, 2002)

Erratum to: Building a mouse model hallmarking the congenital human cytomegalovirus infection in central nervous system - J. L. Tang; M. L. Wang; J. J. Qiu; D. Wu; W. Hu; B. F. Shi; Y. Hu; J. P. Li (Archives of Virology, 2002)

Development and mapping of AFLP markers linked to the sorghum fertility restorer gene rf4 - L. Wen; H. V. Tang; W. Chen; R. Chang; D. R. Pring; P. E. Klein; K. L. Childs; R. R. Klein (Theoretical and Applied Genetics, 2002)

In Vivo Quantification of Blood Flow and Wall Shear Stress in the Human Abdominal Aorta During Lower Limb Exercise - Charles A. Taylor; Christopher P. Cheng; Leandro A. Espinosa; Beverly T. Tang; David Parker; Robert J. Herfkens (Annals of Biomedical Engineering, 2002)

Modern pollen samples from alpine vegetation on the Tibetan Plateau - Ge Yu; Lingyu Tang; Xiangdong Yang; Xiankun Ke; Sandy P. Harrison (Global Ecology and Biogeography, 2001)
A set of 316 modern surface pollen samples, sampling all the alpine vegetation types that occur on the Tibetan Plateau, has been compiled and analysed. Between 82 and 92% of the pollen present in these samples is derived from only 28 major taxa. These 28 taxa include examples of both tree (AP) and herb (NAP) pollen types. Most of the modern surface pollen samples accurately reflect the composition of the modern vegetation in the sampling region. However, airborne dust‐trap pollen samples do not provide a reliable assessment of the modern vegetation. Dust‐trap samples contain much higher percentages of tree pollen than non‐dust‐trap samples, and many of the taxa present are exotic. In the extremely windy environments of the Tibetan Plateau, contamination of dust‐trap samples by long‐distance transport of exotic pollen is a serious problem. The most characteristic vegetation types present on the Tibetan Plateau are alpine meadows, steppe and desert. Non‐arboreal pollen (NAP) therefore dominates the pollen samples in most regions. Percentages of arboreal pollen (AP) are high in samples from the southern and eastern Tibetan Plateau, where alpine forests are an important component of the vegetation. The relative importance of forest and non‐forest vegetation across the Plateau clearly follows climatic gradients: forests occur on the southern and eastern margins of the Plateau, supported by the penetration of moisture‐bearing airmasses associated with the Indian and Pacific summer monsoons; open, treeless vegetation is dominant in the interior and northern margins of the Plateau, far from these moisture sources. The different types of non‐forest vegetation are characterized by different modern pollen assemblages. Thus, alpine deserts are characterized by high percentages of Chenopodiaceae and Artemisia , with Ephedra and Nitraria . Alpine meadows are characterized by high percentages of Cyperaceae and Artemisia , with Ranunculaceae and Polygonaceae. Alpine steppe is characterized by high abundances of Artemisia, with Compositae, Cruciferae and Chenopodiaceae. Although Artemisia is a common component of all non‐forest vegetation types on the Tibetan Plateau, the presence of other taxa makes it possible to discriminate between the different vegetation types. The good agreement between modern vegetation and modern surface pollen samples across the Tibetan Plateau provides a measure of the reliability of using pollen data to reconstruct past vegetation patterns in non‐forested areas.

Helper virus-free HSV-1 vectors packaged both in the presence of VSV G protein and in the absence of HSV-1 glycoprotein B support gene transfer into neurons in the rat striatum - Ju Tang, Tianzhong Yang, Hara P Ghosh, (Journal of NeuroVirology, 2001)

Regulation of body dimethylsulfoniopropionate (DMSP) content by the copepod Temora longicornis : a test of four mechanisms - K. W. Tang; T. D. Fenn; P. T. Visscher; H. G. Dam (Marine Biology, 2000)

Palaeovegetation of China: a pollen data‐based synthesis for the mid‐Holocene and last glacial maximum - G. Yu; X. Chen; J. Ni; R. Cheddadi; J. Guiot; H. Han; S. P. Harrison; C. Huang; M. Ke; Z. Kong; S. Li; W. Li; et al. (Journal of Biogeography, 2000)
Pollen data from China for 6000 and 18,000 14 C yr bp were compiled and used to reconstruct palaeovegetation patterns, using complete taxon lists where possible and a biomization procedure that entailed the assignment of 645 pollen taxa to plant functional types. A set of 658 modern pollen samples spanning all biomes and regions provided a comprehensive test for this procedure and showed convincing agreement between reconstructed biomes and present natural vegetation types, both geographically and in terms of the elevation gradients in mountain regions of north‐eastern and south‐western China. The 6000 14 C yr bp map confirms earlier studies in showing that the forest biomes in eastern China were systematically shifted northwards and extended westwards during the mid‐Holocene. Tropical rain forest occurred on mainland China at sites characterized today by either tropical seasonal or broadleaved evergreen/warm mixed forest. Broadleaved evergreen/warm mixed forest occurred further north than today, and at higher elevation sites within the modern latitudinal range of this biome. The northern limit of temperate deciduous forest was shifted c. 800 km north relative to today. The 18,000 14 C yr bp map shows that steppe and even desert vegetation extended to the modern coast of eastern China at the last glacial maximum, replacing today’s temperate deciduous forest. Tropical forests were excluded from China and broadleaved evergreen/warm mixed forest had retreated to tropical latitudes, while taiga extended southwards to c . 43°N.

Genomic in situ hybridization (GISH) analyses of Thinopyrum intermedium, its partial amphiploid Zhong 5, and disease-resistant derivatives in wheat - S. Tang; Z. Li; X. Jia; P. J. Larkin (Theoretical and Applied Genetics, 2000)

Transcriptional profiling of human microvascular endothelial cells in the proliferative and quiescent state using cDNA arrays - Hua-Tang Zhang; Michael Gorn; Kenneth Smith; Andrew P. Graham; Kelvin K.W. Lau; Roy Bicknell (Angiogenesis, 1999)

Expression of vascular endothelial growth factor (VEGF) and its receptors during embryonic implantation in the golden hamster ( Mesocricetus auratus ) - X. J. Yi; H. Y. Jiang; K. K. H. Lee; W. S. O; P. L. Tang; P. H. Chow (Cell and Tissue Research, 1999)

Control of reactive balance adjustments in perturbed human walking: roles of proximal and distal postural muscle activity - P.-F. Tang; Marjorie H. Woollacott; Raymond K. Y. Chong (Experimental Brain Research, 1998)

Polar cyanobacteria versus green algae for tertiary waste-water treatment in cool climates - Evonne P. Y. Tang; Warwick F. Vincent; Daniel Proulx; Paul Lessard; Joël de la Noüe (Journal of Applied Phycology, 1997)

Anxiolytic-like effects of PNU-101017, a partial agonist at the benzodiazepine receptor - A. H. Tang; S. R. Franklin; D. B. Carter; V. H. Sethy; L. M. Needham; E. J. Jacobsen; P. F. Von Voigtlander (Psychopharmacology, 1997)

Interindividual variation in the enzymatic 15-keto-reduction of 13,14-dihydro-15-keto-prostaglandin E 1 in human liver and in human erythrocytes - P. Rady-Pentek; R. Mueller; B.-K. Tang; W. Kalow (European Journal of Clinical Pharmacology, 1997)

Envelope gene sequences of human T-lymphotropic virus type I in Taiwan - M. T. Lin; Y. C. Chen; P. J. Chen; Y. C. Yang; J. L. Tang; J. M. Wu; S. E. Chuang; C. S. Yang (Archives of Virology, 1996)

Genetic evidence for the existence of cryptic species in theAnopheles albitarsis complex in Brazil: Allozymes and mitochondrial DNA restriction fragment length polymorphisms - S. K. Narang; T. A. Klein; O. P. Perera; José Bento Lima; Amazonia Toda Tang (Biochemical Genetics, 1993)

Genetic evidence for the existence of cryptic species in theAnopheles albitarsis complex in Brazil: Allozymes and mitochondrial DNA restriction fragment length polymorphisms - S. K. Narang; T. A. Klein; O. P. Perera; José Bento Lima; Amazonia Toda Tang (Biochemical Genetics, 1993)

Protein binding, sister chromatid exchange and expression of oncogene proteins in patients treated with cisplatinum (cisDDP)-based chemotherapy - F. Perera; H. K. Fischman; K. Hemminki; P. Brandt-Rauf; H. L. Niman; S. Smith; E. Toporoff; K. O'Dowd; M. X. Tang; W. Y. Tsai; M. Stoopler (Archives of Toxicology, 1990)

Hantavirus strains isolated from rodentia and insectivora in rural China differentiated by polymerase chain reaction assay - Y. W. Tang; S. L. Ruo; A. Sanchez; Susan P. Fisher-Hoch; J. B. McCormick; Z. Y. Xu (Archives of Virology, 1990)

Human stomach alcohol and aldehyde dehydrogenases (ALDH): A genetic model proposed for ALDH III isozymes - S. -J. Yin; T. -C. Cheng; C. -P. Chang; Y. -J. Chen; Y. -C. Chao; H. -S. Tang; T. -M. Chang; C. -W. Wu (Biochemical Genetics, 1988)

Human stomach alcohol and aldehyde dehydrogenases (ALDH): A genetic model proposed for ALDH III isozymes - S. -J. Yin; T. -C. Cheng; C. -P. Chang; Y. -J. Chen; Y. -C. Chao; H. -S. Tang; T. -M. Chang; C. -W. Wu (Biochemical Genetics, 1988)